Plasma membrane H+-ATPase Pma1 regulates growth and virulence in Penicillium digitatum from citrus fruits involving iron homeostasis - Xinyue Lin; Huilin Kang; Shuzhen Yang; Gang Fan; Litao Peng; Hanyu Mu; Yanli Wang (Food Microbiology, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

The multicopper ferroxidase Pdfet3 is essential for reductive iron assimilation, redox homeostasis, and virulence in Penicillium digitatum - Xinyue Lin; Shuzhen Yang; Hanyu Mu; Gang Fan; Litao Peng; Yanli Wang (Physiological and Molecular Plant Pathology, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; Dave W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Bioluminescent enzyme immunoassay for cortisol by exploitation of single-chain variable fragment and single-chain variable fragment-nanoluciferase fusion protein - Xiping Cui; Qiyi He; Huiyi Yang; Mingxia Lin; Suqing Zhao; Yunping Mu (Analytica Chimica Acta, 2026)

Microplastic pollution and ecological risks in the wet season: Potential effects on bacterial communities and nitrogen cycling in a coastal watershed of Southeast China - Yaling Huang; Suofang Zhong; Wantao Lin; Shoufeng Zhang; Hua Jiang; Xuan Wang; Jingli Mu (Marine Pollution Bulletin, 2026)

Nationwide occurrence and site-scale dynamics of antibiotics in landfill-associated waters in China - Lin Mu; Fusheng Zha; Menghe Wen; Qiao Wang; Xiaojin Song (Water Research, 2026)

Supplemental vitamins A, D, and E improve OPU-IVP efficiency in postpartum dairy cows by alleviating oxidative stress - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Acid-catalyzed ethanol pretreatment of sugarcane bagasse enables electrochemically improved hard carbon anodes for sodium-ion batteries - Nethmi Kulanika Dayarathne; Eric Campbell; Mu Xiao; Jiaye Ye; Cheng Yan; Hongxia Wang; Dawei Wang; Yu Lin Zhong; Zhanying Zhang (Chemical Engineering Journal, 2026)

Axial oxygen–coordinated niobium single-atom catalyst enables durable bifunctional oxygen reduction/evolution electrocatalysis in zinc–air batteries - Xueyan Lin; Ngoc Thanh Ngan Thai; Yuwei Zhu; Haiyan Tan; Rishav Baranwal; Linqin Mu; Arunachala Mada Kannan; Jingyue Liu; Bin Wang; Zhaoyang Fan (Chemical Engineering Journal, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Lead exposure in an urban population: isotopic evidence reveals contributions from dietary and inhalation pathways - Shuhui Mu; Jin Wu; Jiaxin Ye; Jiemin Liu; Guangle Qiu; Xiaoyuan Lin; Xiangyang Bi (Applied Geochemistry, 2026)

GnRH supplementation in the PreOvsynch protocol targeting follicular cysts enhances synchronization and reduces days open in dairy cows - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Animal Reproduction Science, 2026)

A dual colorimetric and fluorescent sensor for non-enzymatic glucose detection via catalytic reaction with o-phenylenediamine mediated by carbon dot-decorated Fe3O4 nanoparticles - Wei-Bin Tseng; Wei-Kai Tsai; Ming-Mu Hsieh; Chi-Yu Lu; Po-Chiao Lin; Wei-Lung Tseng (Analytica Chimica Acta, 2026)

Genome-wide investigation of methyl-CpG-binding domain genes in Brassica napus L. and functional characterization of BnaC09.MBD7 and BnaA10.MBD7 in modulating osmotic stress tolerance - Ling Jiang; Gang Lin; Mufei Shi; Jingying Wu; Lixuan Sun; Xiumei Xu; Zhihua Zhang; Shiyao Wen; Meifeng Chen; Xiewang Gao; Mu Xiao (Physiology and Molecular Biology of Plants, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Wave climate characteristics and long-term trends in the northern South China Sea: A 31-year hindcast study for offshore engineering applications - Jinzong Guan; Qianru Niu; Yanqing Feng; Yan Li; Xiaomei Liao; Lin Mu (Ocean Engineering, 2026)

Deoxynivalenol impairs intestinal epithelial proliferation by disrupting the DEK-RPS6KB1 complex to suppress Wnt/β-catenin signaling - Lingjie Zeng; Ruqin Lin; Zhitian Yang; Danni Yu; Jintao Xu; Ziwan Qu; Zhikai Wu; Peiqiang Mu; Jun Jiang; Dongsheng Yao; Jikai Wen; Yiqun Deng (Journal of Environmental Sciences, 2026)

Corrigendum to “Seafloor troughs offshore southwestern Taiwan revealed by AUV and ROV observations” [Geomorphology 512 (2026) 110490] - Tzu-Ting Chen; Charles K. Paull; Char-Shine Liu; Chih-Chieh Su; Ho-Han Hsu; Liang-Fu Lin; David W. Caress; Roberto Gwiazda; Eve Lundsten; Shao-Yung Liu; Ling-Ji Mu; Arif Mirza (Geomorphology, 2026)

Novel ex-situ functionalized bacterial cellulose-based packaging films with full hydrogen-bonded network for sustainable and bio-safety food preservation - Changqing Zhao; Lang Wu; Jiao Huang; Liguo Yin; Jiawei Wang; Zihao Feng; Lin Bai; Xingxiu Zhao; Zhifeng Zhao; Shengdong Mu (Food Research International, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Di(2-ethylhexyl) phthalate (DEHP)-induced circadian disruption accelerates aging-related functional declines via oxidative stress and insulin/IGF-1 signaling in Caenorhabditis elegans - Pei-Ling Yen; Wei Lin Chuah; Sin Ni; Tzu-Ting Chang; Mu-En Huang; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Precision design of hydrogel polymer nanoparticles: How side-chain spatial arrangement and length matching govern antibacterial activity, physiological robustness, and selectivity - Weixiang Zhang; Weicheng Tang; Bo Li; Shiqi Lin; Mu Yuan; Lei Su; Wenfeng Tan; Gailing Yuan; Mingming Liu (Chemical Engineering Journal, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Neural stem cell extracellular vesicle-mediated delivery of astragaloside IV attenuates hypoxic-ischemic brain damage by activating the mTOR pathway - Ruiqin Yu; Huizhong Bai; Yanjun Mo; Gang Liu; Zhuoluo Zhou; Lin Xu; Bowen Deng; Xiaoye Li; Jinyu Li; Houjun Zhang; Xiaohong Mu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Absolute configurations and anti-bacterial activity of two century-old maleidrides - Rongfang Qu; Chenyu Wu; Wenhao Mu; Yuxia Lou; Weibing Jiang; Minfeng Jin; Lin-Fu Liang; Fan Yang (Natural Product Research, 2026)

Impacts of continuous ultra-low temperature freezing on the evolution of pore throat characteristics and coalbed methane production in bituminous coal - Lei Qin; Siheng Lin; Niandong Chen; Feilong Zhang; Zengning Huang; Han Wang; Shiyin Lv; Miao Mu (Journal of Applied Geophysics, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times” [Chem. Eng. J. 537 (2026) 176461] - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

High-Efficiency N-acetylneuraminic acid biosynthesis in plasmid-free Escherichia coli MG1655 - Qian Lin; Yuanlin Liu; Wenbo Zhang; Liping Qiao; Yingying Zhu; Dawei Ni; Wanmeng Mu (Bioresource Technology, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

A label-free fluorescent/electrochemical dual-mode zinc complex biosensor for highly selective and sensitive detection of tetracycline - Zhi-Lin Mu; Zeyu Zhu; Jiale Cheng; Xingyu Zhan; Chen He; Zhongyan Chen; Hong-Ping Xiao; Jing-Yuan Ge (Analytica Chimica Acta, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Nb5+ pre-intercalation synergistically regulates layered vanadates for high-performance aqueous Zn-ion batteries - Shenglin Zhong; Denglian Chen; Xiang Hu; Han Lin; Menghui Mu; Zhenhai Wen; Jiangcong Zhou (Chemical Engineering Journal, 2026)

Analysis of impedance mechanisms in aqueous zinc-ion batteries via electrochemical impedance spectroscopy and distribution of relaxation times - Zetao Chen; Xiyan Wei; Quanyan Man; Jinpeng Guan; Yongbiao Mu; Lin Zeng (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Functional characterization of collectin liver 1 involving antibacterial immunity and inflammation regulation in Oreochromis niloticus - Lu Deng; Xiaoxue Yin; Qingliang Zeng; Zhanyao Lin; Jiadong Li; Siqi Wu; Jianmin Ye; Liangliang Mu (Aquaculture, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Real-time analysis of drillstring dynamic insertion and system vibration-induced wellbore wear in offshore directional well - Feng Tang; Yongsheng Liu; Lin Chai; Zongyang Mu; Xin Lei; Qiang Sun (Ocean Engineering, 2026)

Mutations in PilZ domains of newly discovered bacterial β-(1,3;1,4)-mixed linkage glucan synthases modulate polysaccharide production - Rebecka Karmakar Saldivar; Shu-Chieh Susie Chang; Sheileza Rajkumari; Rico A. Pratama; Yen-Ting Lin; Mu-Rong Kao; Christina Divne; Chi-Kung Ni; Yves S.Y. Hsieh (Carbohydrate Polymers, 2026)

Dark environment affects circadian rhythms of gut bacterial community in the mud crab Scylla paramamosain - Jiazheng Zhou; Weichuan Lin; Qiang Li; Shujian Chen; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Journal of Oceanology and Limnology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Stable methane storage via hydrate-based composite coating systems - Liang Mu; Zijie Chen; Minghu Huang; Xinhan Lin; Qingyan Cui (Journal of Cleaner Production, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

A multiscale perspective on the occurrence, transport mechanisms, and molecular interactions of heavy metals in contaminated soils - Lin Mu; Fusheng Zha; Hua Guo; Mrunal Bokade; Sharad Pandey; Devendra Narain Singh; Qiao Wang; Tianyang Chen; Haodong Tai; Peifu Cai; Kai Huang; Huaxiang Yan (Environmental Research, 2026)

Layered nitrogen application drives changes in nitrogen nutrition status of wheat by affecting key soil microbial clusters - Yang Zhou; Pengjia Wu; Yanjie Qu; Shengyan Pang; Haimeng Mu; Min Yang; Xiang Lin; Dong Wang (European Journal of Agronomy, 2026)

Performance of Wetland in Pollutant Removal: a Review - Yifan Zhuo; Sangar Khan; Wenting Liu; Tingting Hu; Yuke Duan; Zongwei Lin; Xinxin Qi; Collins Oduro; Hongli Mu; Naicheng Wu (Water, Air, & Soil Pollution, 2026)

Advancing African pangolin conservation: a review of research progress and future directions (2006–2024) - Tongtong Gu; Biao Yang; Zixin Lin; Rongxiang Mu; Wanlong Zhu (European Journal of Wildlife Research, 2026)

Evaluation of the effectiveness of indigenous entomopathogenic fungi for controlling chilli thrips (Scirtothrips dorsalis Hood) in blueberry under greenhouse conditions - Hsin-Yu Lin; Yi-Ju Chen; Kusum Mushyakhwo; Chin-Mu Chen; Yu-Shin Nai (BioControl, 2026)

Effects of size grading on growth, survival, metamorphosis, and thermotolerance of two venerid clams (Ruditapes philippinarum and R. variegatus) under farmed conditions - Jinlong Li; Shu Xiao; Xiangzhi Lin; Zhaoping Wang; Zongbao Mu; Xiaodong Zheng (Aquaculture International, 2026)

Highly selective methane recovery from low-concentration coalbed gas using TBPO-promoted hydrate formation - Liang Mu; Minghu Huang; Zijie Chen; Xinhan Lin; Qingyan Cui (Process Safety and Environmental Protection, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Molecular characteristics of water-soluble organic aerosols under pollution conditions in a coal resource-based city revealed by FT-ICR MS: a significant role of sulfur-containing compounds - Chao Zhang; Ziyong Guo; Qingyu Hu; Lin Qi; Yang Chen; Yufeng Zhao; Nan Pei; Wei Sun; Xiaodong Hu; Yuxiang Yang; Fengxian Liu; Ling Mu; et al. (Fuel, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Highland barley arabinoxylans with distinct molecular features modulate retrogradation and in vitro digestibility of highland barley starch - Yonghui Dong; Tingting Mu; Xue Wu; Chunping Chen; Haiyu Wu; Lin Han; Caian He; Min Wang (Food Hydrocolloids, 2026)

Metabolic adaptations in the hypothermic myocardium: Mechanisms and clinical implications - Huimin Wu; Fei Xiao; Yuan Zhang; Huili Li; Mu Jin; Peirong Lin; Fushan Xue; Sheng Wang (Cryobiology, 2026)

Hydroxyl-functionalized electrolyte additives for stable low-temperature zinc-ion battery operation - Zhenzhen Kong; Xiyan Wei; Yongbiao Mu; Jinpeng Guan; Zetao Chen; Lin Yang; Liying Wang; Meisheng Han; Lin Zeng (Chemical Engineering Journal, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Minimal modification to displacement ventilation for significant improvement through air redistribution - Zi Cheng; Jingkai Wang; Zhenying Zhang; Hao Simone Wang; Yibin Lu; Zekai Mu; Jian Liu; Zhang Lin (Building and Environment, 2026)

Bidirectional aeolian erosion controls the spatial variations of yardang landforms in Dunhuang yardang National Geopark, Northwestern China - Yongchong Lin; Chunyao Wu; Guijin Mu; Jifeng Zhang; Cong Zhao (Aeolian Research, 2026)

Insights into co-occurrence characteristics and interplay of microbial communities and environmental pollutants on biofilm-colonized microplastics in mangrove ecosystems - Tao Yang; Xudong Ye; Xi Deng; Jun Mu; Min Liu; Jianhui Lin; Yuangao Qu; Yingxu Zeng (Water Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Enhanced performances of iron-rich sludge ash for chemical looping gasification of pretreated rice straw by the modification of transition metal oxides - Ying Dai; Jinpeng Jiang; Xiran Xu; Meng Sun; Xiaoyuan Wang; Lin Mu; Jianbiao Chen; Yuezhao Zhu; Jinzhu Tan (Fuel, 2026)

NeuProIO: A dual-action solid drug nanoparticle topical formulation for simultaneous intraocular pressure reduction and neuroprotection for glaucoma - Lei Xu; Mu Li; Lin Qi; Tzu-Chen Wang; Dong Liu; Vimalin Jeyalatha Mani; Hsin-Yin Chuang; Qingbo Yang; Ruipu Mu; Samira Mahdi; Da Huang; Honglan Shi; et al. (Chemical Engineering Journal, 2026)

Lithofacies Identification and Classification Based on Least Squares Support Vector Machine Optimized by Sparrow Search Algorithm - Chenyang Mu; Zhongjie Guo; Guangxu Wang; Xiaoxiao Zhang; Cheng Qian; Changsong Lin; Yang Chen; Yougong Wang; Wei Wu (Mathematical Geosciences, 2026)

A lightweight detection algorithm for cereal weed recognition based on deep learning - Xiao-Wei Dong; Lin-Feng Wang; Xi-Mu Zhang; Ming Wang; Wei-Kai Li (Crop Protection, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Transcriptome-wide identification of glycoRNAs by Clier-seq pipeline - Nannan Zhu; Yan-Lin Yang; Yuan-Tao Liu; Zheng-Zhou Lu; Yan Wang; Yi-Ling Luo; Ning Meng; Yan Yuan; Qian Zhong; Mu-Sheng Zeng (Science China Life Sciences, 2026)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Dual identification optical sensor for sodium benzoate and potassium sorbate based on UV-DAS combined with SEP-CNN-TL - Junfeng Wang; Rui Zhu; Jie Gao; Fei Xie; Mu Li; Changyin Li; Yungang Zhang; Hongbin Lin (Food Control, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Three-dimensional molecular engineering of fluorene-based self-assembled monolayers for high-performance inverted perovskite solar cells - Fen Xia; Xiaohan Lin; Jing Zhang; Jun Yin; Jing Li; Xijiao Mu; Song Tu; Binghui Wu; Nanfeng Zheng (Chemical Engineering Journal, 2025)

Self-healing, highly stretchable, recyclable PU-curcumin elastomer with substrate-sensitive solid-state fluorescence - Linjie Wei; Xiubin Xu; Hongchun Mu; Wantong Lin; Jiahui Tang; Jieran Li; Jianwei Liu; Haitao Dong; Danfeng Yu; Xu Wu (Chemical Engineering Journal, 2025)

Predicting internal carotid artery system risk based on common carotid artery by machine learning - Yuhao Tong; Qingyi Zhang; Feng Zhang; Weidong Mu; Steven W. Su; Lin Liu (Medical & Biological Engineering & Computing, 2025)

Downlisting and recovery of species assessed by the IUCN - Mu‐Ming Lin; Richard A. Fuller; In‐Ki Kwon; Kisup Lee; Simba Chan; Wangwang Qiu; Yat‐Tung Yu; Chi‐Yeung Choi (Conservation Biology, 2025)
Despite the increasing number of species assessed for extinction risk by the International Union for Conservation of Nature (IUCN) (163,040 species as of 2024), only about 1 in 1,000 have been downlisted due to genuine population improvement. Although this rare conservation achievement has been widely celebrated in several recent cases, some other downlisting decisions have met with controversy. A primary role of the IUCN is to assess extinction risk. In this role, it must maintain its independence and not be influenced by the public outcry that may occur when a high‐profile species is downlisted, even if well‐established conservation programs may be disrupted or abandoned as a result. We explored the potential positive and negative consequences of downlisting for conservation efforts through case studies of the giant panda ( Ailuropoda melanoleuca ), red‐crowned crane ( Grus japonensis ), saiga antelope ( Saiga tatarica ), and black‐faced spoonbill ( Platalea minor ), which has recently been proposed for downlisting. Although downlisting can enable more effective use of limited resources, these cases highlight potential risks, including weakened legal backing, diversion of resources away from the species, and declining public and political support. The relatively unquestioned downlisting of the saiga antelope illustrates how early and inclusive engagement of local experts, assessors, donors, and other stakeholders can help ensure that decisions are effectively communicated and implemented without jeopardizing species recovery. The IUCN Green Status of Species assessment is a complementary tool to the IUCN Red List and offers a useful measure of conservation progress, which can help decision makers ensure that downlisting does not undermine long‐term conservation efforts.

Splicing factor Nova regulates the splice variants in exons 3 and 6 of GABA receptor subunit RDL from Chilo suppressalis Walker (Lepidoptera: Crambidae) - Zijiao Song; Jie Jiang; Tao Tang; Guanghua Luo; Junyan Wang; Kaixiang Lin; Lili Mu; Chunqing Zhao (Pesticide Biochemistry and Physiology, 2025)

Facile synthesis of high loading and highly electron-delocalized Co single-atom catalyst for PMS activation: An in-depth study of molecular orbital and catalytic mechanisms - Mu Li; Dongsheng Xia; Wei Zhang; Feiyun Sun; Guan Zhang; Lin Lin; Zhengjun Gong; Bing Li; Xiao-yan Li (Journal of Hazardous Materials, 2025)

Optimizing germination to enhance antioxidant and nutritional quality of sunflower seed oil: Role of phenylalanine ammonia-lyase - Zhang Lin; Ziyang Zhao; Zhenkang Yao; Lei Mu; Xiangyu Wang; Yuxuan Liu; Qi Li; Xiuzhu Yu (Food Chemistry, 2025)

Effects of phenological uniformity on prediction accuracy of wheat yield and biomass - Yandong Yang; Qing Li; Qinwen Lin; Huimin Wang; Yi Shi; Gengchen Wu; Yue Mu; Dong Jiang; Seishi Ninomiya (Field Crops Research, 2025)

Synergistic Co single-atom/nanoparticle catalysis enables stable hydrogenation of levulinic acid to gamma-valerolactone with formic acid - He Huang; Wei Zhang; Jianrong Zeng; Mengke Liu; Han Lin; Liwen Mu; Xin Feng; Xiaohua Lu; Lilong Zhang; Jiahua Zhu (Chemical Engineering Journal, 2025)

Elucidating the suppressive role of native bacterial traits against root-knot nematodes to control plant-parasitic effect in serpentine hostile rhizosphere soil - Aslia Asif; Liang-Yu Lin; Ping-Chi Hsu; Suprokash Koner; Zeng-Yei Hseu; Tsui-Kang Hsu; Shih-Wei Huang; Bing-Mu Hsu (Applied Soil Ecology, 2025)

Insufficient telomeric DNA damage response promotes chromosomal instability in aged oocytes - Tianqi Cao; Simiao Liu; Fang Wang; Min Gao; Wenlian Wu; Yanling Qiu; Ming Mu; Tengteng Xu; Jinkun Wen; Yuxi Chen; Haiying Liu; Xiqian Zhang; et al. (Science Bulletin, 2025)

Experimental research on drift of rescue targets in a basin under controllable wind-wave-current environment - Jiaqian Wang; Hao Qin; Haiwen Tu; Daosheng Wang; Zhengzhou Li; Bo Li; Hanxiang Su; Chuanfeng Liu; Lei Qin; Lin Mu (Ocean Engineering, 2025)

Drift trajectory prediction and search area optimization of marine targets based on hybrid optimization algorithm - Nan Zhou; Zhongben Zhu; Hongde Qin; Lin Zhou; Yifan Xue; Xiaokai Mu; Guiqiang Bai (Ocean Engineering, 2025)

The oldest known Curvicubitidae (Hemiptera) from the Permian (Wuchiapingian) of Zhangshu City, Jiangxi Province, southern China - Qian-Qi Zhang; Lin Mu; Lei Zhang; Xu-Heng Du; Hai-Chun Zhang (Palaeoworld, 2025)

Spatio-temporal distribution characteristics and sources of organic carbon in a typical mariculture Bay: A case study of Sansha Bay, China - Xiaolong Lv; Lingyi Lei; Feipeng Wang; Rongmao Li; Cong Li; Hua Lin; Zhi Zhang; Jingli Mu (Marine Environmental Research, 2025)

Hydrogel-engineered platforms for efficient solar interfacial evaporation: Current status and future directions - Junnan Jiang; Heyu Jin; Yao Lu; Xiaohua Liu; Hongyu Ge; Lin Mu (Journal of Water Process Engineering, 2025)

Urban-rural inequality in lung cancer risk from indoor air pollution: Prolonged indoor time amplifies the risks of solid fuel use - Ruimin Yang; Xinlin Mu; Guilian Wang; Deliang Tang; Bin Wang; Zhiwen Li; Haidong Kan; Nan Lin; Shu Tao (Journal of Environmental Management, 2025)

Optimizing biogas residue composting: Impact of biochar and zeolite co-loaded with lignocellulose-degrading microbial agents on degradation, humification, and microbial ecology - Hong Chang; Ruian Lin; Xiaohong Su; Xinrui Xu; Wei Liu; Yilin Zhang; Zeyan Mu; Xin Wang; Anina James; Junting Pan (Journal of Environmental Chemical Engineering, 2025)

Imbalanced starch and protein accumulation during grain filling under salt stress leads to increased protein components in rice grains - Zheng Huang; Lin Li; Yicheng Zhang; Yixue Mu; Ye Tao; Zhenxiang Zhou; Lixiao Nie (Field Crops Research, 2025)

NMR study on the distribution pattern of pore water in the process of freeze-thaw permeability enhancement of coal - Lei Qin; Pengfei Liu; Haifei Lin; Hui Wang; Ruizhe Wang; Miao Mu; Niandong Chen; Chengang Sun (Engineering Geology, 2025)

Spirulina-derived atomically dispersed Fe–N4 sites on g-C3N4 for efficient CO2 photoreduction - Haoxian Wang; Junjie Wang; Jin Xu; Jingkai Lin; Zhongshuai Zhu; Yazi Liu; Feihu Mu; Bin Huang; Fei Yu; Chenmin Xu; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2025)

Dual-ion charge storage mechanism in polypyrrole cathodes for zinc-ion hybrid capacitors - Jiali Zhang; Tao Xue; Yongbiao Mu; Hongjie Li; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Synergistic engineering of porous P-doped CuS/CNTs composite as high-performance conversion anode for aqueous zinc-ion batteries - Chuanjin Lin; Guoquan Suo; Jiarong Li; Rongrong Mu; Laraib Habib; Xiaojiang Hou; Xiaohui Ye; Yanling Yang (Chemical Engineering Journal, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Spatiotemporal dynamics of retrogressive thaw slumps on the Qinghai-Tibet Plateau: integrating UAV-LiDAR and GPR - Fan Yu; Jing Luo; Fujun Niu; Zhanju Lin; Bingyan Li; Yanhu Mu; Xin Ju; Minghao Liu; Guoan Yin; Zeyong Gao; Xiaolong Zhao; Chengming Zhang (Landslides, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

PRDM14 promoted NSCLC cell proliferation, migration and invasion via modulating H3K27me3-mediated PEBP1/Raf-1/MEK/ERK MAPK signaling - He Shi; Yunfei Jiang; Haijun Mu; Guohua Liu; Xinyue Cheng; Weili Kong; Xingqi Zhou; Xiaoqiang Wen; Xiao Wang; Yiyu Lin; Linyu Pan; Haiying Dong; et al. (Genes & Genomics, 2025)

Influence of track ground pressure distribution uniformity on traction under slope - Xiaodong Mu; Zonglin Li; Yuxuan Ji; Zhijie Liu; Zheng Wang; Luojia Duan; Shiying Chen; Xiaoyan Zhu; Zhong Lin; Fuzeng Yang (Biosystems Engineering, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Damage and acoustic characteristics of water-saturated coals with different ranks under liquid nitrogen freezing and thawing treatments - Lei Qin; Jiawei Li; Haifei Lin; Shugang Li; Miao Mu; Shiyin Lv; Niandong Chen (Geomechanics for Energy and the Environment, 2025)

Impact of marine chlorine emissions on secondary organic aerosols in North China Plain - Zhaoqi Gao; Lin Li; Zhou Liu; Jiangshan Mu; Zhuyi Wang; Bin Luo; Jingzhu Zhang; Shuting Tang; Hongliang Zhang; Jianlin Hu; Xuan Wang; Xuehua Zhou; et al. (Environmental Pollution, 2025)

The association between maternal exposure to ten neonicotinoid insecticides and preterm birth in Guangxi, China - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Xiaogang Wang; Qian Liao; Lidi Lei; Shun Liu; Dongping Huang; Xiaoqiang Qiu; Xiaoyun Zeng (Environmental Pollution, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Hybrid electrospun fibers with metal-based catalysts for zinc-air battery: Recent development and future perspectives - Mahmood ul Haq; Yongbiao Mu; Saz Muhammad; Baoxin Wu; Kejun Yan; Jiahui Luo; Zheng Li; Zhiqing Tang; Muhammad Ajmal; Wenjia Li; Lin Zeng (Chemical Engineering Journal, 2025)

Atomically dispersed noble metal-Ox sites for electrocatalytic chlorine evolution - Chen Chen; Baoyi Guo; Tingting Liu; Ruting Lin; Yuyu Liu; Qiufeng Huang; Xiaofeng Zhang; Jiabao Huang; Fangren Qian; Shengyun Huang; Qingjun Chen; Xueqin Mu; et al. (Chemical Engineering Journal, 2025)

Contaminant transport in a municipal solid waste landfill: On-site assessment and numerical modelling of vertical barrier wall effectiveness - Lin Mu; Qiao Wang; Fusheng Zha; Jun Wang; Rumin Xu; Miao Piao (Waste Management, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Effects of Lactobacillus plantarum on Broiler Health: Integrated Microbial and Metabolomics Analysis - Lei Wang; Fazul Nabi; Xiaohu Zhang; Guangyu Zhou; Qurban Ali Shah; Siyuan Li; Yaozhong Lu; Siyang Mu; Xiaohui Zhu; Zhengrong Lin; Jiakui Li (Probiotics and Antimicrobial Proteins, 2025)

Drift Characteristics and Predictive Modeling of Life Rafts in Island and Reef Waters - Zhengzhou Li; Xiangyu Tang; Chenzhuo Hu; Haiwen Tu; Lin Mu (Journal of Marine Science and Engineering, 2025)
Accurate prediction of drifting trajectories is essential for improving the operational efficiency of maritime search and rescue (SAR), particularly within the complex geomorphological settings of island and reef regions, such as those in the South China Sea. This study investigates the drift characteristics of life rafts under varying loading conditions across both open-sea and island–reef regions. Comprehensive field experiments were conducted over 15 days in the waters around the Wanshan Archipelago, using advanced instruments to collect wind, current, and drift trajectory data. Based on these observations, two models—the AP98 leeway model and a BP neural network model—were developed and validated. The results show that the AP98 model performs better in open-sea conditions, whereas the BP neural network provides more accurate predictions in island and reef areas with complex environmental factors. A Monte Carlo simulation was also integrated to enhance the robustness of drift area predictions. These findings offer valuable insights into life raft drift behavior in complex marine environments and provide technical support for improving SAR operations in island–reef regions.

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

A high-performance flexible coaxial BTO/PAN piezoelectric nanofibers for facial expression analysis - Junfei Lin; Junbin Yu; Fangyuan Chen; Xuying Jia; Jiahe Li; Juanhong Zhao; Jian He; Xiaojuan Hou; Jiliang Mu; Xiujian Chou (Chemical Engineering Journal, 2025)

Identifying the Alkaline Tolerance-Related Genes Through Transcriptome Analysis of Halomonas alkalicola CICC 11012 s - Lei Zhai; Shuaicheng Mu; Ruina Liu; Rui Liu; Geer Lin; Qi Han; Su Yao (Current Microbiology, 2025)

LINE-1 DNA methylation mediates smoking-related risk in site-specific urothelial carcinoma: a Taiwan case–control study - Chien-Hung Lin; Peir-Haur Hung; Chao-Hsiang Chang; Han Chang; Mu-Chi Chung; Wen-Chi Chang; Chi-Jung Chung (Archives of Toxicology, 2025)

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Predicting and regulating potential zone for heavy metal re-contaminated farmland: Case study in Taiwan - Jieh-Haur Chen; Mu-Chun Su; Meng-Fen Yeh; Wei-Jen Lin; Tzuyang Yu; Ming-Chung Yeh (Environmental Development, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Quasi-Solid-State Electrolytes: Bridging the gap between solid and liquid electrolytes for zinc-ion batteries - Tao Xue; Jinpeng Guan; Yongbiao Mu; Meisheng Han; Chao Yang; Limin Zang; Lin Zeng (Chemical Engineering Journal, 2025)

Insight into dysregulated VEGF-related genes in diabetic retinopathy through bioinformatic analyses - Xiaoguang Wang; Xianglian He; Zhen Li; Tao Mu; Lin Pang; Weiguo Ma; Xuejun Hu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Corrigendum to “Recirculating aquaculture system as microbial community and water quality management strategy: a rearing mode for improved viability of crab larvae” [Water Research Volume 252, Mar 2024] - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of neonicotinoid pesticide exposure in the first trimester on gestational diabetes mellitus based on interpretable machine learning - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Yonghong Sheng; Yang Xu; Dongping Huang; Shun Liu; Xiaoyun Zeng; Virasakdi Chongsuvivatwong; Xiaoqiang Qiu (Environmental Research, 2025)

Rational application of QoIs fungicides to achieve a rice-fungi-fish interaction balance within paddy ecosystems - Hong Li; Xueqing Wang; Beixing Li; Jin Lin; Feng Liu; Wei Mu (Environmental Pollution, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Transcriptomics with metabolomics reveals the mechanism of alkaline tolerance in Halomonas alkalicola CICC 11012s - Ruina Liu; Geer Lin; Qi Han; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Archives of Microbiology, 2025)

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

Time-Series models for ground subsidence and heave over permafrost in InSAR Processing: A comprehensive assessment and new improvement - Chengyan Fan; Cuicui Mu; Lin Liu; Tingjun Zhang; Shichao Jia; Shengdi Wang; Wen Sun; Zhuoyi Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Analysis of the Alkaline Resistance Mechanism of Halomonas alkalicola CICC 11012 s by Proteomics and Metabolomics - Ruina Liu; Qi Han; Geer Lin; Shuaicheng Mu; Shuang Liu; Su Yao; Lei Zhai (Current Microbiology, 2025)

Mitochondrial mechanism of florfenicol-induced nonalcoholic fatty liver disease in zebrafish using multi-omics technology - Lin Zhang; Yang Du; Yameng Li; Tiancai Wang; Yecan Pan; Xiaofeng Xue; Xiyan Mu; Jing Qiu; Yongzhong Qian (Journal of Hazardous Materials, 2025)

Regulation of 2-acetyl-1-pyrroline (2-AP) biosynthesis and grain quality in fragrant rice under salt stress - Lin Li; Zheng Huang; Yicheng Zhang; Yixue Mu; Yusheng Li; Lixiao Nie (Field Crops Research, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

Combination mechanism and dimethyl ether removal performance of organic-bound water in kitchen waste - Jipeng Sun; Wei Zhu; Jun Zhong; Biao Mu; Xin Wang; Xinyi Wang; Yucheng Xu; Jun Cao; Naixi Lin (Waste Management, 2025)

Water-in-water emulsions stabilized by konjac glucomannan/tragacanth gum hydrogels for riboflavin delivery - Nitong Bu; Huanglong Lin; Di Zhang; Xianrui Chen; Pingping Tan; Yuanbo Zhong; Liying Huang; Jie Pang; Lin Wang; Ruojun Mu (Journal of Food Engineering, 2025)

Integrating machine learning for multi-objective optimization of biomass conversion to hydrogen - Yinchen Li; Peng Jiang; Lin Li; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Journal of Cleaner Production, 2025)

Construction of diffusion and binding synergy in carbon-supported catalysts with varied Pd0/PdO Ratios for direct synthesis of hydrogen peroxide - Zhiheng Wang; Jiali Huang; Guancong Jiang; Tuo Ji; Han Lin; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Chemical Engineering Journal, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Thiol-linked hyaluronic acid-mediated encapsulation of RCR-stabilized gold nanoclusters for hyaluronidase sensing and cellular imaging - Manivannan Madhu; Meng-Yuan Tsai; Ming-Mu Hsieh; En-Yu Lin; Wei-Bin Tseng; Chi-Yu Lu; Wei-Lung Tseng (Carbohydrate Polymers, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Modeling of wave-induced drift based on stepwise parameter calibration - Kui Zhu; Xueyao Chen; Lin Mu; Dingfeng Yu; Runze Yu; Zhaolong Sun; Tong Zhou (Frontiers in Marine Science, 2025)
The motion of waves in water causes the slow movement of drifting sea targets—a phenomenon usually ignored in target-drift prediction models for maritime search and rescue (SAR). This study examined the wave-induced drift’s influence on field-observation experiments involving two common, differently sized SAR targets—an offshore fishing vessel (OFV) and a person in the water (PIW)—using parameter stepwise calibration and machine-learning (ML) methods. The sample of wave-induced drift velocity was obtained by gradually separating current-induced (CI) drift’s and wind-induced (WI) drift’s influence from the target-drift velocity using the least-square method and AP98 model. A force analysis method and three ML methods, long short-term memory (LSTM), back-propagation (BP) neural network, and random forest (RF), were used to fit the wave-induced drift velocity by combining eight different parameter schemes. Finally, the drift trajectories considering the influence of waves were fitted and verified based on 2 independent samples respectively. Compared with the force analysis method, the accuracy of the ML methods in the verification test was higher. In addition, the results show that for OFVs, considering wave-induced drift’s influence in the ensemble-trajectory prediction could improve the simulation accuracy. However, for a PIW, no significant improvement was observed. This result also indicates that wave-induced drift may not be simply ignored in large SAR targets’ drift prediction.

Dietary supplementation of Roseovarius litoreus improves survival and immune defense of the swimming crab Portunus trituberculatus - Mingming Niu; Weichuan Lin; Qingyang Wu; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Modification of salivary multilayer for improved oral lubrication - Pingping Tan; Huanglong Lin; Yuanbo Zhong; Jianshe Chen; Ruojun Mu (Trends in Food Science & Technology, 2025)

Effect of microplastics concentration and size on pollutants removal and antibiotic resistance genes (ARGs) generation in constructed wetlands: A metagenomics insight - Lin Liang; Weiliang Pan; Merui Mu; Lin Zhang; Xiangyu Yang; Ruina Zhang; Lianfeng Du; Xuan Guo (Journal of Hazardous Materials, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Phase-separated anisotropic PVA hydrogel loaded with tetramethylpyrazine for spinal cord injury repair - Gang Liu; Shenglin Li; Bowen Deng; Luyao Huo; Huizhong Bai; Shengyuan Jiang; Yimin Zhou; Zhenzhen Pei; Ceren Kimna; Yi Zhao; Lin Xu; Jinyu Li; et al. (Chemical Engineering Journal, 2025)

Interaction between resveratrol and SIRT1: role in neurodegenerative diseases - Lin Zhu; Miaomiao Yang; Lehao Fan; Qiuying Yan; Lifeng Zhang; Ping Mu; Fangjin Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Endoplasmic reticulum stress and Ca2+ dysregulation in response to ammonia nitrogen exposure could be alleviated by dietary fermented mulberry leaf meal in Megalobrama amblycephala - Wenqiang Jiang; Linjie Qian; Qiaoqiao Mu; Yan Lin; Siyue Lu; Zhengyan Gu; Huaishun Shen; Xianping Ge; Linghong Miao (Aquaculture, 2024)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Iron-Induced vacancy and electronic regulation of nickle phosphides for ampere-level alkaline water/seawater splitting - Linbo Jiang; Lintao Jiang; Xu Luo; Ruidong Li; Qingqu Zhou; Lin Wang; Lei Chen; Shichun Mu (Chemical Engineering Journal, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

A real time data-driven dynamic glasius bionic neural network path planning algorithm for polar under-ice feature scanning by “Xinghai 1000” AUV - Lin Zhou; Zhongchao Deng; Guiqiang Bai; Nan Zhou; Hongde Qin; Zhongben Zhu; Yifan Xue; Xiaokai Mu; Xiaojian Cao (Ocean Engineering, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Constructed wetland coupled microbial fuel cell (CW-MFC) with Phragmites australis planted for hexavalent chromium removal and electricity generation - Chunxia Mu; Kelei Huang; Lin Wang (Journal of Water Process Engineering, 2024)

Differential impacts of small hydropower plants on macroinvertebrate communities upstream and downstream under ecological flow - Zongwei Lin; Xinxin Qi; Mali Li; Yuke Duan; Huimin Gao; Guohao Liu; Sangar Khan; Hongli Mu; Qinghua Cai; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Small hydropower plants affect aquatic community diversity: A longitudinal study under ecological flow - Xinxin Qi; Zongwei Lin; Huimin Gao; Mali Li; Yuke Duan; Guohao Liu; Sangar Khan; Hongli Mu; Beata Messyasz; Naicheng Wu (Journal of Environmental Management, 2024)

Alternate wetting and drying maintains rice yield and reduces global warming potential: A global meta-analysis - Lin Li; Zheng Huang; Yixue Mu; Shaokun Song; Yicheng Zhang; Ye Tao; Lixiao Nie (Field Crops Research, 2024)

Transgenerational and parental impacts of acrylamide exposure on Caenorhabditis elegans: Physiological, behavioral, and genetic mechanisms - Yajuan Chen; Zihan Liu; Weijia Yuan; Shan Lu; Weidong Bai; Qinlu Lin; Jianfei Mu; Jianqiang Wang; Haifang Wang; Ying Liang (Environmental Pollution, 2024)

Oncogenic miRNAs dependent photothermal-immunotherapy enhanced by on-demand manipulation of immunosuppressive microenvironment using engineered gold nanoparticles for effective treatment of primary and metastatic tumor - Li Chen; Yu Hu; Wenyun Mu; Tao Liu; Wenjun Tang; Lin Weng; Yanmin Zhang; Xin Chen (Chemical Engineering Journal, 2024)

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

Application of Fluorescent Composite Materials as a Sustained Release System in Treatment of Polycystic Ovary Syndrome - Lin Wang; Liangshan Mu; Yao Ye; Jun Xu; Xutong Zou (Journal of Fluorescence, 2024)

Insights into the individual and combined effects of Cu(Ⅱ) and Ni(Ⅱ) on anammox: Nitrogen removal performance, enzyme activity and microbial community - Minghao Mu; Dengzhi Li; Shilin Lin; Haisong Bi; Xinqiang Liu; Zheng Wang; Chengduo Qian; Junyuan Ji (Chemosphere, 2024)

Facing the solid waste of cotton straw and plastic mulch film mixture in China: Centralized or decentralized pyrolysis facility? - Hao Zhang; Peng Jiang; Guanhan Zhao; Lin Li; Minjiao Chen; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Waste Management, 2024)

Optimization of latching control for duck wave energy converter based on deep reinforcement learning - Haowen Su; Hao Qin; Zhixuan Wen; Hongjian Liang; Haoyu Jiang; Lin Mu (Ocean Engineering, 2024)

Cobalt-doped copper sulfide nanocomposite integrated with graphene oxide as a high-performance conversion anode for aqueous zinc-ion batteries - Rongrong Mu; Guoquan Suo; Chuanjin Lin; Jiarong Li; Shazam Javed; Xiaojiang Hou; Xiaohui Ye; Yanling Yang; Li Zhang (Chemical Engineering Journal, 2024)

Structural characterisation and anti-colon cancer activity of an arabinogalactan RSA-1 from Raphani semen - Qi Li; Shuang Jiang; Qianbo Wang; Jiahui Sun; Zhibin Wang; Xiaotong Wang; Xuepeng Shi; Yuanqiu Mu; Lin Wei; Chunjuan Yang (Carbohydrate Polymers, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Essential trace element and phosphatidylcholine remodeling: Implications for body composition and insulin resistance - Wen-Ling Lin; Mu-Ming Chien; Sangopas Patchara; Weu Wang; Amelia Faradina; Shih-Yi Huang; Te-Hsuan Tung; Chien-Sung Tsai; Anatoly V. Skalny; Alexey A. Tinkov; Chun-Chao Chang; Jung-Su Chang (Journal of Trace Elements in Medicine and Biology, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

A culture-dependent analysis of anaerobic methylotrophs in oil reservoir systems - Lin-Yuan Huang; Yi-Fan Liu; Wan-Qi Qin; Shi-Yi Wang; Yuan-Hao Wang; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2024)

A systematic investigation of PVDF-HFP in perovskite solar cells for improved space mission reliability - Seoungjun Ahn; Wei-Hao Chiu; Wei-Chen Chu; Pei-Yu Chen; Ting-Han Lin; Kun-Mu Lee (Chemical Engineering Journal, 2024)

Non-negligible Effect of Native Rhizobacteria on Cooperation with Plant Growth Regulators Improve Tolerance to Cadmium: A Case Study Using Duckweed Spirodela polyrhiza as Indicating Plant - Demei Mu; Weitie Lin; Jianfei Luo (Journal of Plant Growth Regulation, 2024)

Inclusion of Lonicerae flos improved anaerobic fermentation and antioxidant activity of mixed silage (agro-residue and alfalfa) - Lin Mu; Xin Cao; Yating Wang; Qinglan Wang; Zhifei Zhang (Animal Feed Science and Technology, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Dynamic mechanism of CO2 capture from flue gas via hydrate-based method induced by using IB group transition metal functionalized carbon nanotubes - Fang Wang; Wenjing Lin; Jinchi Mu; Xiaosheng An; Ruiyang Zhang; Lihong Guo; Ying Zhou (Gas Science and Engineering, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Dual-Targeting EGCG/NO-Supplying protein assembled nanoparticles with Multi-Synergistic effects against atherosclerosis - Chi Lin; Tsai-Mu Cheng; Yun-Chun Liu; Fang-Yu Hsu; Chun-Ming Shih; Min-Lang Tsai; Chun-Che Shih; Fwu-Long Mi (Chemical Engineering Journal, 2024)

SIRT1-Mediated HMGB1 Deacetylation Suppresses Neutrophil Extracellular Traps Related to Blood–Brain Barrier Impairment After Cerebral Venous Thrombosis - Shuwen Mu; Ziqi Li; Long Lin; Di Wang; Fei Yang; Li Chen; Liang Xian; Kunzhe Lin; Yinghong Lin; Dan Ye; Yang Yang; Liangfeng Wei; et al. (Molecular Neurobiology, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Upcycling of waste polycarbonate to recyclable Poly(carbonate-imines) with exceptional thermal properties and unprecedented flame retardancy - Yi-Chun Chen; Pin-Qi Mu; Kamani Sudhir K. Reddy; Ru-Jong Jeng; Mahdi M. Abu-Omar; Ching-Hsuan Lin (Chemical Engineering Journal, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Reassembly and biotic sources of carapace bacterial community of Portunus trituberculatus after host molting - Weichuan Lin; Jiameng Chen; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2024)

Environmental and human history in the hyper-arid eastern Tarim Basin (Lop Nur), northwest China: A critical review for sustaining the natural and cultural landscapes - Kangkang Li; Xiaoguang Qin; Bing Xu; Lei Zhang; Guijin Mu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Hongjuan Jia; Zhiqiang Yin; et al. (Quaternary International, 2024)

The preparation of synbiotic AHY relieving loperamide-induced constipation and its modulation mechanism in vivo - Lai Jiang; Rui Zhang; Xudong Lin; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Climate change, corporate risk-taking, and financialization: evidence from Chinese A-share non-financial listed companies - Lin Zheng; Qiguang An; Mu Yang (Environment, Development and Sustainability, 2024)
Climate change-induced risks, such as global warming, can affect the economic development of entities and, consequently, the stability of financial markets. Businesses are progressively making the transition to green in order to lessen the negative consequences of climate threats. This study examines the relationship between corporate risk-taking (CRISK) and financialization (FIN) in light of climate change. The impact of business risk-taking on financialization is experimentally investigated through the transmission chain of “CRISK - enterprise value – FIN” using a fixed-effects model. The study also analyzes the moderating effect of climate change on the direct and indirect channels of climate change by using “temperature” and “investors’ concern about climate,” respectively. In addition, the empirical results are tested for robustness using propensity score matching and an instrumental variable method. This study’s findings reveal the following key insights. First, CRISK significantly enhances FIN by improving firm value. Second, enterprises with high financing constraints and manufacturing enterprises are more likely to have a positive correlation between CRISK and FIN. Third, the relationship between CRISK and FIN is enhanced by the direct transmission channel of increasing climate risk, but the indirect transmission channel is not significant. This study proposes policy recommendations to address the effect of climate risk on CRISK and FIN. Among these suggestions are the prudent distribution of financial resources among enterprises according to their level of risk-taking and the reinforcement of regulatory authorities’ financial oversight of businesses with high financing constraints and the manufacturing sector. By implementing these policies, companies can better manage climate-related risks and contribute to financial stability.

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Optimizing the deployment of LID facilities on a campus-scale and assessing the benefits of comprehensive control in Sponge City - Xianbao Zha; Wei Fang; Wei Zhu; Shuangtao Wang; Yong Mu; Xiaofeng Wang; Pingping Luo; Mohd Remy Rozainy Mohd Arif Zainol; Mohd Hafiz Zawawi; Khai Lin Chong; Apip Apip (Journal of Hydrology, 2024)

Mechanism of peroxymonosulfate activation by nanoparticle Co@N–C: Experimental investigation and theoretical calculation - Mu Li; Lin Lin; Wei Zhang; Yubin Zou; Jiahui Hu; Yin Li; Bing Li; Feiyun Sun; Xiao-yan Li (Chemosphere, 2024)

Experimental and numerical investigation on the interaction between rogue waves and a KVLCC2 in head sea - Jiaqian Wang; Hao Qin; Weiyi Zhang; Haoran Zhang; Lin Mu (Ocean Engineering, 2024)

Equilibrium Mg and K isotope fractionation between carnallite and saturated brine: Calibrations and applications - Zhiguang Xia; Yongjie Lin; Dongdong Li; Lars Reuning; Zhongya Hu; Chuan Liu; Jun Mu; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Jurassic integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Jianguo Li; Xin Rao; Lin Mu; Xiaohui Cui; Xin Li; Hui Luo; Peixue Liu (Science China Earth Sciences, 2024)

Effect of use of NSAIDs or steroids during the acute phase of pain on the incidence of chronic pain: a systematic review and meta-analysis of randomised trials - Luyao Huo; Gang Liu; Bowen Deng; Lin Xu; Yanjun Mo; Shengyuan Jiang; Jingwei Tao; Huizhong Bai; Li Wang; Xiaoxiao Yang; Jizhou Yang; Xiaohong Mu (Inflammopharmacology, 2024)
Background This study is the first to summarize the evidence on how the use of anti-inflammatory drugs during acute pain has an impact on the development of chronic pain. Methods Randomized controlled trials retrieved from nine databases included anti-inflammatory drugs (NSAIDs or steroids) versus non-anti-inflammatory drugs in patients with acute pain and reported the incidence of chronic pain. No specified date, age, sex, or language restrictions. Subgroup analyses were performed according to pain classification, follow-up time, and medication. The GRADE method was used to evaluate quality of evidence. Results A total of 29 trials (5220 patients) were included. Steroids or NSAIDs did not reduce the incidence of chronic nociceptive pain. Steroid use in acute phase significantly reduced the incidence of chronic neuropathic pain. In subgroup analysis, benefits were observed for methylprednisolone and dexamethasone, with some adverse effects. Steroids or NSAIDs were statistically significant in reducing pain intensity over 1 year, but the effect size was too small, and whether the long-term effect is clinically relevant needs to be further studied. Conclusion Quality of the evidence was low to moderate. No drug can be recommended to prevent chronic nociceptive pain. Injections of steroids (methylprednisolone or dexamethasone) during the acute phase reduce the incidence of chronic neuropathic pain, but most included studies also used local anesthetics. The results are indirect and need to be interpreted with caution. The pooled data effect sizes for pain intensity were small, so the clinical relevance was unclear. Study registration PROSPERO (CRD42022367030).

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Storm surge risk assessment and sensitivity analysis based on multiple criteria decision-making methods: a case study of Huizhou City - Wei Wei; Shining Huang; Hao Qin; Lichen Yu; Lin Mu (Frontiers in Marine Science, 2024)
Coastal areas face escalating storm surge disasters due to rising sea levels and urban growth, posing greater risks to lives and property. Comprehensive storm surge risk assessment and sensitivity analysis in coastal areas are crucial for effective disaster prevention and mitigation. This research focuses on Huizhou, China, conducting a comparative study of storm surge risk assessment and sensitivity analysis based on an integrated approach, which includes the storm surge inundation numerical model (FVCOM-SWAN), Geographic Information System (GIS) and Remote Sensing (RS) techniques, and Multiple Criteria Decision-Making (MCDM) methods. Ten flood-related risk indicators are selected from the hazard, exposure and vulnerability, the weights of which are evaluated through a comprehensive comparison among Analytic Hierarchy Process (AHP), Fuzzy Analytic Hierarchy Process (FAHP), Entropy Weight (EW), AHP-EW, and FAHP-EW methods. High-precision risk level maps are generated subsequently utilizing GIS and RS techniques. Sensitivities of the indicators are analyzed using One-At-A-Time (OAT) and Fourier Amplitude Sensitivity Test (FAST) methods. The proposed storm surge risk assessment framework, the MCDM comparative study and the sensitivity analysis can offer insights for better understanding and management of storm surge risks, and contribute to the standardization and application of storm surge risk assessment.

Changes in Sea Level along the South China Sea Coast Based on the Homogenized Tide Gauge Data - Yan Li; Lin Mu; Dawei You; Jiaying Wang; Qianru Niu; Xiaomei Liao (Journal of Marine Science and Engineering, 2024)
To estimate the changes in the annual mean sea level (MSL) and extreme sea levels (ESLs), the largest collection of tide gauge records from 10 tidal stations along the northern coast of the South China Sea (SCS) were analyzed in this study. Here, all the tide gauge records had been homogenized by a two-step process involving the detection of inhomogeneities, that is, breakpoints caused by non-climatic changes and the application of the adjustment. The study’s conclusions, based on the homogenized tide gauge records, can be summarized as follows: The instrument change and station relocation are the main causes for the identified inhomogeneities. From 1989 to 2018, the sea level along the SCS was at an average rate of 4.0 mm per year, as measured by the homogenized tide gauges. The ESLs from the nine tidal stations rose notably with interannual fluctuations, except for the XSA station. Additionally, the ESLs exhibited substantial decadal variations. The ESLs rose along the northern coast of the SCS and were accelerated at most stations throughout the whole study period, especially after the 1980s. There were significant positive correlations between the ESL and the annual MSL at most tide gauges. The MSL’s changes, especially long-term changes, play an important role in the change in ESLs.

Recirculating aquaculture system as microbial community and water quality management strategy in the larviculture of Scylla paramamosain - Zhibin Lu; Weichuan Lin; Qiang Li; Qingyang Wu; Zhiming Ren; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Water Research, 2024)

Tetramethylpyrazine inhibits the inflammatory response by downregulating the TNFR1/IκB-α/NF-κB p65 pathway after spinal cord injury - Gang Liu; Luyao Huo; Bowen Deng; Shengyuan Jiang; Yi Zhao; Yanjun Mo; Huizhong Bai; Lin Xu; Chuanyu Hu; Xiaohong Mu (Toxicology and Applied Pharmacology, 2024)

Brunonianines A-C, C20-diterpenoid alkaloids with cyano group from Delphinium brunonianum Royle - Qing Li; Zhi-Wei Wang; Mu-Xuan Wang; Hao-Lin Yu; Lei Chen; Zhuoer Cai; Yu Zhang; Min-Min Gu; Yuan-Ling Shao; Hong-Ping Han; Zhi-Xin Liao (Phytochemistry, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Research on the Drift Prediction of Marine Floating Debris: A Case Study of the South China Sea Maritime Drift Experiment - Lin Mu; Haiwen Tu; Xiongfei Geng; Fangli Qiao; Zhihui Chen; Sen Jia; Ruifei Zhu; Tianyu Zhang; Zhi Chen (Journal of Marine Science and Engineering, 2024)
Annually, hundreds of individuals tragically lose their lives at sea due to shipwrecks or aircraft accidents. For search and rescue personnel, the task of locating the debris of a downed aircraft in the vastness of the ocean presents a formidable challenge. A primary task these teams face is determining the search area, which is a critical step in the rescue operation. The movement of aircraft wreckage on the ocean surface is extremely complex, influenced by the combined effects of surface winds, waves, and currents. Establishing an appropriate drift motion prediction model is instrumental in accurately determining the search area for the wreckage. This article initially conducts maritime drift observation experiments on wreckage, and based on the results of these experiments, analyzes the drift characteristics and patterns of the debris. Subsequently, employing a wealth of observational experimental data, three types of drift prediction models for the wreckage are established using the least squares method. These models include the AP98 model, the dynamics model, and an improved model. In conclusion, the effectiveness and accuracy of the three models is evaluated and analyzed using Monte Carlo techniques. The results indicate that the probability of positive crosswind leeway (CWL) is 47.4%, while the probability of negative crosswind leeway (CWL) is 52.6%. The jibing frequency is 7.7% per hour, and the maximum leeway divergence angle observed is 40.4 degrees. Among the three drift prediction models, the refined AP98 drift model demonstrates the highest forecasting precision. The findings of this study offer a more accurate drift prediction model for the search of an aircraft lost at sea. These results hold significant guiding importance for maritime search and rescue operations in the South China Sea.

Acetylenic spiroketal enol ethers from Artemisia rupestris and their synergistic antibacterial effects on methicillin-resistant Staphylococcus aureus - Chuan-Yun Xiao; Jiang-Er Lan; Xiao Liu; Zhong-Lin Sun; Xiao-Jin Li; Yi-Han Yin; Simon Gibbons; Qing Mu (Natural Product Research, 2024)

Construction land reduction projects as a pathway to sustainability: an empirical analysis of risks factors in China - Bingxu Mu; Yuming Zhu; Naveed Ahmad; Jiahe Zhou; Lei He; Hongli Lin (Environmental Science and Pollution Research, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

The resource curse in least developed countries: The roles of foreign direct investment, energy efficiency, and electricity access - Ling Lin; Mu Li; Xinmeng Hou; Arsalan Zahid Piprani (Resources Policy, 2024)

Influence of inertinite on coal physicochemical thermal transformation properties and liquefaction behaviors - Wenchao Qian; Chunyang Yan; Xiaoyin Mu; Jiahao Chen; Lulu Cui; Hualin Lin; Sheng Han; Zongqing Bai (Fuel, 2024)

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

BioTreasury: a community-based repository enabling indexing and rating of bioinformatics tools - Qi Zhao; Xin Zhou; Jingxing Wu; Jieyi Cai; Xiaoqiong Bao; Lin Tang; Chaoye Wang; Chunlei Liu; Yukai Wang; Yuyan Teng; Mohan Zheng; Weiping Mu; et al. (Science China Life Sciences, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

A novel Vibrio alginolyticus phage and its therapy application in Portunus trituberculatus larvae - Ruqian Cai; Dengfeng Li; Weinan Qin; Wei Lin; Lingting Pan; Minhua Qian; Fei Wang; Chunlin Wang; Changkao Mu; Yigang Tong (Aquaculture, 2024)

Deciphering microbial communities and their unique metabolic repertoire across rock-soil–plant continuum in the Dayoukeng fumarolic geothermal field of the Tatun Volcano Group - Jung-Sheng Chen; Bashir Hussain; Hsin-Chi Tsai; Viji Nagarajan; Rajendran Senthil Kumar; I-Ching Lin; Bing-Mu Hsu (Environmental Science and Pollution Research, 2023)

An update on the effects of food-derived active peptides on the intestinal microecology - Jianfei Mu; Qinlu Lin; Ying Liang (Critical Reviews in Food Science and Nutrition, 2023)

Record-breaking marine heatwave in northern Yellow Sea during summer 2018: Characteristics, drivers and ecological impact - Yan Li; Guoyu Ren; Qingyuan Wang; Lin Mu; Qianru Niu; Hanxiang Su (Science of The Total Environment, 2023)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Heterostructured YFeO3/CeO2 as efficient photoelectrode for photoelectrochemical degradation of organic pollutants under visible light irradiation - Yen-Shen Kuo; Mu-Jung Lin; Cheng-Liang Hsu; Yi-Hung Liu (Journal of Water Process Engineering, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

Improved solid/liquid separation performance of hydrochar from sludge via hydrothermal carbonization - Jun Zhong; Wei Zhu; Biao Mu; Jipeng Sun; Xin Wang; Naixi Lin; Jun Cao (Journal of Environmental Management, 2023)

Side chain modulated carbazole-based bifunctional hole-shuttle interlayer simultaneously improves interfacial energy level alignment and defect passivation in high-efficiency perovskite solar cells - Yuan-Yu Chiu; Shih-Hsuan Chen; Kun-Mu Lee; Tz-Feng Lin; Ming-Chung Wu (Chemical Engineering Journal, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Somatic embryo induction and plantlet regeneration of Canna × generalis from immature zygotic embryo - Zu-yan Gan; Mu-lin Shu; Feng Yang; Guo-fang Wang; Wen-e Zhang; Xue-jun Pan (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Application and evaluation of layering shear method in LADCP data processing - Zijian Cui; Chujin Liang; Binbin Guo; Feilong Lin; Yong Mu (Acta Oceanologica Sinica, 2023)

Thiocarbonyl fluoride generated in situ from difluorocarbene for cyclization of vicinal X-H substituted amines (X = N, O or S) - Jia-Lu Hu; Mu-Xian Fu; Ji-Chang Xiao; Jin-Hong Lin (Journal of Fluorine Chemistry, 2023)

Historical and projected evolutions of glaciers in response to climate change in High Mountain Asia - Lin Yang; Guangju Zhao; Xingmin Mu; Yanli Liu; Peng Tian; Puqiong; Danzengbandian (Environmental Research, 2023)

Graphene-based biomimetic array film for simultaneous fog water harvesting and wind power generation - Tsung Han Huang; Mu-Jie Shih; Yi-Yun Chen; Hannah Faye M. Austria; Owen Setiawan; Chunrui Wu; Xiaolong Lu; Lin Zhang; Wei-Song Hung (Chemical Engineering Journal, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Study on the performance of downhole axial cyclone with spiral fins for drainage and sand removal - Huizhen Liang; Jian Ma; Chengzhen Li; Lin Mu; Xiukun Jiang (Journal of Environmental Chemical Engineering, 2023)

Improving the yield and tetracycline adsorption performance of kitchen waste biochar through subcritical dimethyl ether pretreatment - Jipeng Sun; Wei Zhu; Jun Cao; Jun Zhong; Biao Mu; Xin Wang; Naixi Lin (Journal of Environmental Chemical Engineering, 2023)

Improvement of catalytic activity of sorbose dehydrogenase for deoxynivalenol degradation by rational design - Danyang Li; Guoqiang Liang; Peiqiang Mu; Jinquan Lin; Jiarun Huang; Chongwen Guo; Yang Li; Ruqin Lin; Jun Jiang; Jun Wu; Yiqun Deng; Jikai Wen (Food Chemistry, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

Regime Shifts in the Damage Caused by Tropical Cyclones in the Guangdong–Hong Kong–Macao Greater Bay Area of China - Manli Zheng; Lin Mu; Wenjuan Li; Fei Wang; Yan Li (Journal of Marine Science and Engineering, 2023)
Tropical cyclones (TCs) pose a significant threat in terms of wind-induced damage and storm risk to the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) of China. In this research, annual power dissipation index (PDI) and storm surge and wave destructive potential (SDP) index from June to November were used to estimate the damage caused by the TC events in the buffer zone of the GBA. The regime shifts in 1993 and 2013 were identified through the Bayesian changepoint detection in six TC datasets. The TC-induced damage during 1994–2012 (the low-damage period) was weaker than that in 1977–1993 and 2013–2020 (the high-damage periods). The intensity and size of stronger TCs are the dominant factors responsible for the interdecadal changes in the TC damage. This may be explained by the influences of sea surface temperature (SST), surface latent heat flux and mid-level relative humidity. During high-damage periods, TCs can extract more energy from the ocean, leading to increased TC intensity and larger size. Conversely, during low-damage periods, TCs undergo a decrease in energy intake, resulting in reduced TC power and smaller size. The variations in the SST are relative to the Luzon Strait transport. In addition, the reduction in TC translation speed is unfavorable for the development of TCs in low-damage periods. Further research suggested that mid-level steering flow affects the TC movement velocity. The results offer valuable insights into the variations in the TC-induced damage in the GBA.

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Deadlock in transition to a net-zero socially robust knowledge - Kuei-Tien Chou; Mu-Xing Lin; David Walther (Environmental Science & Policy, 2023)

Electricity facilitates the lithium sorption from salt-lake brine by H3LiTi5O12 nanoparticles: Kinetics, selectivity and mechanism - Qiuyue Wang; Mu Li; Bing Zhao; Boyang Meng; Wutong Chen; Zekai Jiang; Xin He; Bing Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2023)

Protective effect of solanesol in glucose-induced hepatocyte injury: Mechanistic insights on oxidative stress and mitochondrial preservation - Yiqiu Liu; Musen Lin; Xingrui Mu; Lin Qin; Junyu Deng; Ye Liu; Xingqian Wu; Wenjie He; Huiwen Pang; Felicity Han; Chengxin Sun; Xuqiang Nie (Chemico-Biological Interactions, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Seismic behaviour of plate-reinforced composite coupling beams with RC slabs - Jianbo Tian; Yong Zhao; Penggang Tian; Wengeng Ren; Zhe Li; Lin Mu; Junlong Lu (Soil Dynamics and Earthquake Engineering, 2023)

Probabilistic modelling of surface drift prediction in marine disasters based on the NN–GA and ARMA model - Kui Zhu; Lin Mu; Runze Yu; Xiaoyu Xia; Haiwen Tu (Ocean Engineering, 2023)

Air quality health index (AQHI) based on multiple air pollutants and mortality risks in Taiwan: Construction and validation - Mu-Jean Chen; Yue Leon Guo; Pinpin Lin; Hung-Che Chiang; Pau-Chung Chen; Yu-Cheng Chen (Environmental Research, 2023)

The health risk of acetochlor metabolite CMEPA is associated with lipid accumulation induced liver injury - Wei-Guo Wang; Mu-Yao Li; Lin Diao; Cheng Zhang; Li-Ming Tao; Wei-Xing Zhou; Wen-Ping Xu; Yang Zhang (Environmental Pollution, 2023)

Engineered metal coverage of anode catalyst layer enhancing cell reversal tolerance for proton exchange membrane fuel cells - Zheng Li; Haodong Huang; Yameng Wang; Yongbiao Mu; Yuting Jiang; Qing Zhang; Tianshou Zhao; Lin Zeng (Chemical Engineering Journal, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Parameterization modeling for wind drift factor in oil spill drift trajectory simulation based on machine learning - Darong Liu; Yan Li; Lin Mu (Frontiers in Marine Science, 2023)
Marine oil spill simulations typically employ the oil particle method to calculate particle trajectories, considering various factors such as wind, current, and turbulence. The wind drift factor (WDF), a random element determining the proportion of wind’s effect on oil particles, is often empirically set as a constant in traditional oil spill models, introducing limitations. This study proposes a support vector regression-based parameterization modeling (SVR-PM) for the WDF. Using extensive buoy data and ocean hydrodynamic reanalysis data, we trained an SVR model to compute the WDF in real-time based on real-time wind speed. The SVR-PM was integrated into an oil spill model to enhance the computation of the wind-induced velocity term. We validated the model using satellite images of two significant oil spills, resulting in an excellent average agreement. The SVR-PM’s advantage lies in enhancing the accuracy of wind-induced velocity term in oil spill simulations and demonstrating strong adaptability and generalizability over time and space. This advancement holds significant implications for maritime departments and emergency disaster response units.

An artificial interfacial layer with biomimetic ionic channels towards highly stable Li metal anodes - Yiju Li; Tianshuai Wang; Junjie Chen; Xudong Peng; Minghui Chen; Bin Liu; Yongbiao Mu; Lin Zeng; Tianshou Zhao (Science Bulletin, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Insight into the structural feature, ash transformation behavior, and alkali metal heat release characteristic of industrial lignin via experimental and equilibrium evaluation - Hongchao Yin; Xiankun Huang; Lin Mu; Xi Xi; Ming Dong; Zhaoyi Huo (Fuel, 2023)

Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Real-time model for wave attenuation using active plate breakwater based on deep reinforcement learning - Hongjian Liang; Hao Qin; Lin Mu; Haowen Su (Ocean Engineering, 2023)

Optimum trim prediction for container ships based on machine learning - Haiwen Tu; Kai Xia; Enjin Zhao; Lin Mu; Jianglong Sun (Ocean Engineering, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Enhancement of the release of phenolic compounds from white and black Qingke bran by autoclaving and fermentation treatments - Caian He; Xiaojiao Liu; Haiyan Zhang; Tingting Mu; Yuhong Zhang; Xuechun Ren; Lin Han; Min Wang (Food Bioscience, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Response of soil erosion to vegetation restoration and terracing on the Loess Plateau - Peng Tian; Xiaojing Tian; Ren Geng; Guangju Zhao; Lin Yang; Xingmin Mu; Peng Gao; Wenyi Sun; Yulin Liu (CATENA, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

Understanding stakeholder relationships in sustainable brownfield regeneration: a combined FAHP and SNA approach - Hongli Lin; Yuming Zhu; Jiahe Zhou; Bingxu Mu; Caihong Liu (Environment, Development and Sustainability, 2023)

Derivation and validation of soil cadmium thresholds for the safe farmland production of vegetables in high geological background area - Demiao Mu; Shunan Zheng; Dasong Lin; Yingming Xu; Ruyin Dong; Penggang Pei; Yuebing Sun (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Adaptive changes of swimming crab (Portunus trituberculatus) associated bacteria helping host against dibutyl phthalate toxification - Weichuan Lin; Yimin He; Ronghua Li; Changkao Mu; Chunlin Wang; Ce Shi; Yangfang Ye (Environmental Pollution, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

Investigation on the formation mechanism of main products from TBBPA pyrolysis using DFT method - Xin Mu; Yao Wang; Jinbao Huang; Lin Lan; Hong Wang; Weiwei Xu; Xinsheng Li (Chemosphere, 2023)

The structural model of coal is studied by quantum chemistry calculation and separation of coal liquefied oil group components - Xiaoyin Mu; Wenchao Qian; Chunyang Yan; Hualin Lin; Sheng Han (Fuel, 2023)

Research and demonstration on reclaimation of chemical industrial wastewater with high salinity and hardness and purification of reverse osmosis concentrates - Mu Liu; Zehua Li; Mengyuan Duan; Yingqiang Su; Xiaofeng Lin; Huiming Han; Kai Sun (Desalination, 2023)

ROS filter coating scaffold protects 3D mesenchymal stem cell spheroids for dual-phase treatment of spinal cord injury - Jian Cao; Jiahe Wu; Jiafu Mu; Lingmin Lin; Xunqi Zhang; Tianchen Huang; Teng Ma; Manning Zhu; Xiaoyang Dai; Xuhua Wang; Shiqing Feng; Jian-Qing Gao (Chemical Engineering Journal, 2023)

The preliminary study of exosomes derived from thymosin beta 4-treated adipose-derived stem cells in fat grafting - Wandi Li; Yan Yang; Xiaoyu Zhang; Yan Lin; Haoran Li; Yu Yao; Dali Mu (Genes & Genomics, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Atmospheric dustfall exhibits consistent sedimentary sorting with height evidenced by grain size characteristics - Yongchong Lin; Guijin Mu; Xue Zhao; Lishuai Xu; Jifeng Zhang (Science of The Total Environment, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Comparative investigation on the pyrolysis of crop, woody, and herbaceous biomass: Pyrolytic products, structural characteristics, and CO2 gasification - Lin Mu; Ranyu Wang; Pengwei Xie; Yonglin Li; Xiankun Huang; Hongchao Yin; Ming Dong (Fuel, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Quantitative transport and immobilization of cadmium in saturated-unsaturated soils with the combined application of biochar and organic fertilizer - Zhuowen Meng; Shuang Huang; Wenting Mu; Jingwei Wu; Zhongbing Lin (Environmental Science and Pollution Research, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

An assessment of rainfall kinetic energy functional relationships with GPM DPR - Jayalakshmi Janapati; Balaji Kumar Seela; Pay-Liam Lin; Chen-Hau Lan; Chuan-Chi Tu; Utpal Kumar; Mu-Qun Huang (Journal of Hydrology, 2023)

Long-term environmental risks of the Baltic Sea's "memory effect" revealed by ocean modeling and observation of reprocessing-derived radiotracers - Mu Lin; Jun She; Jens Murawski; Xiaolin Hou; Jixin Qiao (Journal of Hazardous Materials, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Validation and accuracy analysis of wind products from scatterometer onboard the HY-2B satellite - Sheng Yang; Bo Mu; Haoqiang Shi; Chaofei Ma; Wu Zhou; Juhong Zou; Mingsen Lin (Acta Oceanologica Sinica, 2023)

Influence of ionized saline water on soil water and salt transport in saline soils - Kai Wei; Shudong Lin; Jihong Zhang; Quanjiu Wang; Yi Guo; Weiyi Mu (Irrigation and Drainage, 2023)
The utilization of saline water plays an important role in agricultural production in saline areas to overcome freshwater shortages. Ionized saline water might alleviate the adverse effects of salinity on soil and plants. In this study, field experiments were conducted to study the effect of ionized saline water on the soil water content and salinity distribution in a sandy soil under a surface emitter. Passing groundwater through an ionization system installed on a feeding pipeline resulted in producing ionized saline water. Three emitter discharges (1.0, 1.8, 3.1 L h −1 ) and two water types (non‐ionized and ionized saline water) were considered in the experiments. As a result of using ionized saline water, soil water content and salt leaching increased. Ionized treatment increased the salinity desalination rate by 31, 33 and 26% for surface soil layer in comparison with non‐ionized treatments of 1.0, 1.8 and 3.1 L h −1 , respectively. It was found that using ionized saline water could decrease the surface wetting radius by 6–9% and increase the wetting depth by 11–17%. A discharge rate of 1.8 L h −1 was recommended as the optimal discharge rate for ionized saline water under drip irrigation. The results indicated that saline water could be improved through ionized treatment for agricultural irrigation in saline soils in an arid region.

Spatial scale‐dependent dilution effects of biodiversity on plant diseases in grasslands - Xiang Liu; Yao Xiao; Ziyuan Lin; Xingxing Wang; Kui Hu; Mu Liu; Yimin Zhao; Yanwen Qi; Shurong Zhou (Ecology, 2023)
The rapid biodiversity losses of the Anthropocene have motivated ecologists to understand how biodiversity affects infectious diseases. Spatial scale is thought to moderate negative biodiversity–disease relationships (i.e., dilution effects) in zoonotic diseases, whereas evidence from plant communities for an effect of scale remains limited, especially at local scales where the mechanisms (e.g., encounter reduction) underlying dilution effects actually work. Here, we tested how spatial scale affects the direction and magnitude of biodiversity–disease relationships. We utilized a 10‐year‐old nitrogen addition experiment in a Tibetan alpine meadow, with 0, 5, 10, and 15 g/m 2 nitrogen addition treatments. Within the treatment plots, we arranged a total of 216 quadrats (of either 0.125 × 0.125 m, 0.25 × 0.25 m or 0.5 × 0.5 m size) to test how the sample area affects the relationship between plant species richness and foliar fungal disease severity. We found that the dilution effects were stronger in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, compared with 0.5 × 0.5 m quadrats. There was a significant interaction between species richness and nitrogen addition in the 0.125 × 0.125 m and 0.25 × 0.25 m quadrats, indicating that a dilution effect was more easily observed under higher levels of nitrogen addition. Based on multigroup structural equation models, we found that even accounting for the direct impact of nitrogen addition (i.e., “nitrogen‐disease hypothesis”), the dilution effect still worked at the 0.125 × 0.125 m scale. Overall, these findings suggest that spatial scale directly determines the occurrence of dilution effects, and can partly explain the observed variation in biodiversity–disease relationships in grasslands. Next‐generation frameworks for predicting infectious diseases under rapid biodiversity loss scenarios need to incorporate spatial information.

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Filling the gap between molecular and aggregate states: how does molecular packing affect photophysical properties? - Xu-Min Cai; Yuting Lin; Zhenguo Tang; Xuedan Zhang; Tianqi Mu; Shenlin Huang; Zheng Zhao; Ben Zhong Tang (Chemical Engineering Journal, 2023)

Evaluation of soil erosion rates in the hilly-gully region of the Loess Plateau in China in the past 60 years using global fallout plutonium - Yixuan Liu; Xiaolin Hou; Jixin Qiao; Weichao Zhang; Miao Fang; Mu Lin (CATENA, 2023)

Prediction of Groundwater Quality Using Seven Types of First-Order Univariate Grey Model in the Chishan Basin, Taiwan - Tzu-Yi Pai; Ray-Shyan Wu; Ching-Ho Chen; Huang-Mu Lo; Terng-Jou Wan; Min-Hsin Liu; Wei-Cheng Chen; Yi-Ping Lin; Chun-Tse Hsu (Water, Air, & Soil Pollution, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Determining the drift characteristics of open lifeboats based on large-scale drift experiments - Haiwen Tu; Lin Mu; Kai Xia; Xiaodi Wang; Kui Zhu (Frontiers in Marine Science, 2022)
Lifeboat is one of the most important life-saving equipment for escaping at sea when a ship is abandoned in an extreme emergency. An accurate drift model can help rescuers find the drift position of lifeboat in the shortest time, thus improving the efficiency of marine search and rescue (SAR) at sea and ensuring the safety of wrecked people. The purpose of this paper is to investigate the drift characteristics and to develop an accurate drift prediction model for the open lifeboat. First, large-scale drift experiments were conducted to analyze the drift characteristics with three 6.5-meter-long real-size open lifeboats in the South China Sea. Next, three drift prediction models of the lifeboats were developed using the least squares method based on the drift experimental data. Finally, the drift prediction models of the lifeboats were compared and evaluated using the Lagrangian method and Monte Carlo technique, respectively. Results indicate that the probability of positive crosswind leeway (CWL) of the open lifeboat is 47.5%. The jibing frequency is 6% per hour, and the maximum leeway divergence angle is 45°. These drift characteristics are very important for the prediction of the open lifeboat drift trajectory. The comparison results of three drift models show that the improved drift model is more accurate than the other two drift models for predicting drift trajectories of the open lifeboat, which can be directly applied to maritime search and rescue operations in the South China Sea.

Hepatocyte steatosis inhibits hepatitis B virus secretion via induction of endoplasmic reticulum stress - Qichuang Liu; Maoyuan Mu; Huan Chen; Guoyuan Zhang; Yanqing Yang; Jun Chu; Ying Li; Fangwan Yang; Shide Lin (Molecular and Cellular Biochemistry, 2022)

Effects of tillage and cropping sequences on crop production and environmental benefits in the North China Plain - Wen-Xuan Liu; Wen-Sheng Liu; Mu-Yu Yang; Yu-Xin Wei; Zhe Chen; Ahmad Latif Virk; Rattan Lal; Xin Zhao; Hai-Lin Zhang (Environmental Science and Pollution Research, 2022)

New phenolic glycosides from Anemone chinensis Bunge and their antioxidant activity - Zeng-Guang Zhang; Yuan-Yuan Li; Bin Lin; Pei-Pei Guan; Yu Mu; Wen-Jun Qiao; Jing-Sheng Zhang; Xue-Shi Huang; Li Han (Natural Product Research, 2022)

Sestrin2 attenuates renal damage by regulating Hippo pathway in diabetic nephropathy - Yawei Bian; Chonglin Shi; Shan Song; Lin Mu; Ming Wu; Duojun Qiu; Jiajia Dong; Wei Zhang; Chen Yuan; Dongyun Wang; Zihui Zhou; Xuan Dong; et al. (Cell and Tissue Research, 2022)

Toxicokinetics and metabolism of deoxynivalenol in animals and humans - Yu Sun; Jun Jiang; Peiqiang Mu; Ruqin Lin; Jikai Wen; Yiqun Deng (Archives of Toxicology, 2022)

The utilization of physically based models and GIS techniques for comprehensive risk assessment of storm surge: A case study of Huizhou - Si Wang; Lin Mu; Hao Qin; Lizhe Wang; Zhenfeng Yao; Enjin Zhao (Frontiers in Marine Science, 2022)
Quantitative analyses of storm surge risk, which are mostly focused on physical vulnerability, have been widely used to help coastal communities mitigate impacts and damage. Such assessments, however, overlook the social aspect of vulnerability in storm surge risk. By considering both the community’s social vulnerability and buildings’ physical vulnerability, this study proposed a methodology that incorporates social vulnerability into the framework for making quantitative risk assessments of storm surge using a coupled hydrodynamic and wave model, Geographical Information System (GIS) techniques, and the Principal Component Analysis (PCA) method. The coastal area of Huizhou was chosen as the case study due to its high concentration of oil and gas infrastructure in China’s southern Guangdong Province. By combining hazard, exposure, physical vulnerability, and social vulnerability, it was possible to explore the effect of social vulnerability on the physical vulnerability-based risk assessment of storm surge and determine the overall risk level. First, the Gumbel distribution was utilized to establish five representative and plausible hypothetical typhoon events with different return periods (10, 20, 50, 100, and 1000 years) for the study area. Then, using the well-validated fully-coupled model, the Simulating Waves Nearshore (SWAN) model and the ADvanced CIRCulation (ADCIRC) model, storm surge simulations for defined return periods were run, and the geographical distribution of the maximum surge elevations displayed on a GIS platform was used to assess hazard levels. In terms of the physical aspect, the depth-damage functions for buildings were established to estimate direct economic losses and assign risk levels accordingly. For the social vulnerability of a community, a composite score was computed using the PCA method by combining and aggregating indicators representing various characteristics of the social group. The results show that the overall risk level, taking into account both social vulnerability and physical vulnerability, has decreased on average. It suggests that social vulnerability-based risk assessment may account for a significant portion of the overall risk assessment, which is frequently overlooked in traditional storm surge risk assessment. Additionally, the comprehensive and precise risk maps can assist local policymakers in identifying areas at different risk levels and developing evacuation plans, thereby minimizing potential losses, especially in high-risk areas.

The differential impact of air pollutants on acute urticaria and chronic urticaria: a time series analysis - Jiawei Li; Guoqiang Song; Zhenzhen Mu; Xiaoou Lan; Fan Yang; Lin Li; Xiuping Han (Environmental Science and Pollution Research, 2022)

Residual analysis of QoI fungicides in multiple (six) types of aquatic organisms by UPLC-MS/MS under acutely toxic conditions - Hong Li; Shuai Hu; Fengshou Sun; Qi Sun; Ning Wang; Beixing Li; Nan Zou; Jin Lin; Wei Mu; Xiuyu Pang (Environmental Science and Pollution Research, 2022)

Tropical and Polar Oceanic Influences on the Cold Extremes in East Asia: Implications of the Cold Surges in 2020/2021 Winter - Xiaoyu Tan; Linhao Zhong; Lin Mu; Zhaohui Gong (Journal of Marine Science and Engineering, 2022)
East-Asia winter cooling and the associated atmospheric and oceanic influences were investigated based on the wintertime daily temperature and circulation fields during 1950–2020. Both the case study on the 2020/2021 cold surge and the large-sample clustering in the recent 71 winters extracted similar circulation signatures for East-Asia cooling, which are featured by the blocking-related anticyclonic circulation in North Eurasia, large-scale mid-to-high-latitude wave trains, decrease in the sea surface temperature (SST) in tropical Pacific, and the sea-ice cover (SIC) reduction in the Barents and Kara Seas (BKS). From the joint clustering of Eurasian circulation and temperature, two circulation modes that have a cooling effect on East Asia account for 41% of winter days. One of the two modes is characterized by the cyclonic circulation over Northeast Asia coupled with a southward-extending negative-phase Arctic Oscillation (AO−), whose cooling effect is mainly concentrated in central Siberia. The other cooling mode, featuring an anticyclonic circulation over the Urals and AO+ in middle-to-high latitudes, has a relatively stronger cooling effect on lower latitudes, including Mongolia and North China. In general, the occurrences of the mode with warming/cooling effect on East Asia show an overall downward/upward trend. The two cooling modes are significantly influenced by the La Niña-type SST anomaly and reduced SIC in BKS through large-scale wave trains, of which the tropical oceanic forcing mainly acts as a climatic background. Furthermore, the polar forcing is more tightly bound to internal atmospheric variability. Therefore, the tropical SST tends to exert impact over a seasonal scale, but the SIC influence is more significant below the intraseasonal scale; moreover, the synergy between the tropical and polar oceanic forcing can increase the East-Asia cooling days by 3–4% and cold extremes by 5%, mainly through enhancing the AO-related circulation mode.

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Growth of non‐English‐language literature on biodiversity conservation - Shawan Chowdhury; Kristofer Gonzalez; M. Çisel Kemahlı Aytekin; Seung‐Yun Baek; Michał Bełcik; Sandro Bertolino; Sjoerd Duijns; Yuqing Han; Kerstin Jantke; Ryosuke Katayose; Mu‐Ming Lin; Elham Nourani; et al. (Conservation Biology, 2022)
English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on biodiversity conservation published from 1980 to 2018 in English and 15 non‐English languages. We compared the growth rate in publications across languages. In 12 of the 15 non‐English languages, published conservation articles significantly increased every year over the past 39 years, at a rate similar to English‐language articles. The other three languages showed contrasting results, depending on the search system. Since the 1990s, conservation science articles in most languages increased exponentially. The variation in the number of non‐English‐language articles identified among the search systems differed markedly (e.g., for simplified Chinese, 11,148 articles returned with local search system and 803 with Scopus). Google Scholar and local literature search systems returned the most articles for 11 and 4 non‐English languages, respectively. However, the proportion of peer‐reviewed conservation articles published in non‐English languages was highest in Scopus, followed by Web of Science and local search systems, and lowest in Google Scholar. About 20% of the sampled non‐English‐language articles provided no title or abstract in English; thus, in theory, they were undiscoverable with English keywords. Possible reasons for this include language barriers and the need to disseminate research in countries where English is not widely spoken. Given the known biases in statistical methods and study characteristics between English‐ and non‐English‐language studies, non‐English‐language articles will continue to play an important role in improving the understanding of biodiversity and its conservation.

Discovery of the non‐cosmopolitan lineages in Candidatus Thermoprofundales - Yi‐Fan Liu; Liu Yang; Zhong‐Lin Liu; Jing Chen; Bo Fang; Lei Zhou; Jin‐Feng Liu; Shi‐Zhong Yang; Ji‐Dong Gu; Bo‐Zhong Mu (Environmental Microbiology, 2022)
Summary The recently proposed order Candidatus Thermoprofundales, currently containing only one family‐level lineage Marine Benthic Group‐D (MBG‐D), is distributed in global subsurface ecosystems and ecologically important, but its diversity, evolution and metabolism remain largely unknown. Here we described two novel family‐level specialized lineages in Ca . Thermoprofundales, JdFR‐43 and HyVt, which are restricted to specific biotopes (primarily in marine hydrothermal vents and occasionally in oil reservoirs and hot springs) in contrast to the cosmopolitan lineage MBG‐D. The comparative genomics revealed that the specialized lineages have streamlined genomes, higher GC contents, enriched genes associated with nucleotide biosynthesis, ribosome biogenesis and DNA repair and additional thermostable aminopeptidases, enabling them to adapt to high‐temperature habitats such as marine hydrothermal vents, deep subsurface oil reservoirs and hot springs. On the contrary, the unique metabolic traits of the cosmopolitan MBG‐D, motility, glycolysis, butanoate metabolism, secondary metabolites production and additional genes for specific peptides and carbohydrates degradation potentially enhance its response to environmental change. Substrate preference is found for most MAGs across all lineages with the ability to utilize both polysaccharides (chitin and starch) and proteinaceous substances, whereas JdFR‐43 members from oil reservoirs can only utilize proteins. These results expand the diversity of C a . Thermoprofundales significantly and further improve our understandings of the adaptations of C a . Thermoprofundales to various environments.

Quantifying the Spatial Characteristics of the Moisture Transport Affecting Precipitation Seasonality and Recycling Variability in Central Asia - Linhao Zhong; Lijuan Hua; Zhaohui Gong; Yao Yao; Lin Mu (Advances in Atmospheric Sciences, 2022)

Optimization of aquaculture sustainability through ecological intensification in China - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
As the world's leading producer of farmed aquatic food products, China faces great uncertainty concerning the further sustainable development of its aquaculture industry due to high and increasing pressure from environmental and resource constraints. To realize truly sustainable development, it is imperative to establish an evaluation system that integrates social, economic, environmental and resource criteria, and optimizes aquaculture systems through a holistic approach. Here, we used analytical hierarchy processes combined with expert judgment and objective data to assess the sustainability of 10 major aquaculture production systems (APSs) in China. Based on the evaluation results, we propose the ecological intensification of aquaculture systems (ELIAS), rationally integrating anthropogenic inputs with aquaculture ecosystem services, to improve the sustainability of APSs. The holistic evaluation system and ELIAS are fundamental and critical for the future development of aquaculture in China and globally.

Cover Image, Volume 14, Issue 3 - Shuang‐lin Dong; Yun‐wei Dong; Ling Cao; Johan Verreth; Yngvar Olsen; Wen‐jing Liu; Qi‐zhi Fang; Yan‐gen Zhou; Li Li; Jing‐yu Li; Yong‐tong Mu; Patrick Sorgeloos (Reviews in Aquaculture, 2022)
The cover image is based on the Review Article Optimization of aquaculture sustainability through ecological intensification in China by Shuang‐lin Dong et al., https://doi.org/10.1111/raq.12648 image

Detection of the Sinking State of Liquid Oil in Breaking Waves Based on Synthesized Data: A Behavior Process Study of Sunken and Submerged Oil - Shibiao Fang; Lin Mu; Kuan Liu; Darong Liu (Journal of Marine Science and Engineering, 2022)
In computer vision, pollutant detection is a highly concerning issue, and it has been widely used in the fields of pollutant identification, tracking, and precise positioning. In the ocean, oil tends to disperse into the water column as droplets under breaking waves, and it is called sunken and submerged oil. Aiming at the most difficult issue of identifying liquid submerged oil pollution, this paper proposes a method of synthesized data containing specific markers for oil detection. The Canny operator was used to remove the background of the liquid submerged oil. Then, affine transformation was applied to simulate the real situation of oil deformation. Linear mapping was presented by matrix multiplication, and translation was represented by vector addition. At last, bilinear interpolation was used to integrate the oil into the image of the laboratory pictures. In addition, this research randomly added interference information, so that the probability distribution of synthesized data was closer to the probability distribution of the real data. Then, this paper combined various methods to improve the accuracy of liquid oil detection, such as Feature Pyramid Networks, RoIAlign, difficult sample mining. Based on the above methods, 1838 images were synthesized in this paper and combined into a training set. The results show that the average accuracy of the oil detection is increased by 79.72%. The accuracy of the synthesized data method for labeled oil detection was 18.56% higher than that of oil detection without labeling. This research solves the difficulty of obtaining sunken and submerged oil images and the high cost of image annotation.

Composition, Demographic History, and Population Structures of Trichiurus - Kui-Ching Hsu; Mu-Rong Yi; Sui Gu; Xiong-Bo He; Zhi-Sen Luo; Bin Kang; Hung-Du Lin; Yun-Rong Yan (Frontiers in Marine Science, 2022)
Sequences of the complete mitochondrial cytochrome oxidase subunit I gene were used to identify Trichiurus species and examine their population genetic structure and demographic history along the coast of China. Three Trichiurus species were found. Trichiurus japonicus lives in colder waters along the continental shelves in the China Seas, while Trichiurus nanhaiensis lives warmer waters along continental slopes in the South China Sea, and Trichiurus brevis lives in shallow and warmer waters in the South China Sea. The migrations of these species were mainly associated with feeding and spawning preferences. Two major wintering and spawning grounds in the East China Sea and South China Sea were found. All species showed a lack of population genetic structure resulting from their oceanodromous life cycle (the degree of population substructure index N ST = 0.000–0.149), but the results of approximate Bayesian computational approaches suggested population declines or stabilization and differentiation. The results of the T MRCA (time to the most recent common ancestor) showed that during glaciations, the Yellow Sea and the East China Sea were completely exposed, and the South China Sea acted as a refugium. Thus, the populations of these three species experienced differentiation during glaciations. This study also examined the limitations of Bayesian skyline plot analysis.

IgE Reactivity of Potential Allergens from the Swimming Crab Portunus trituberculatus and the Research of ELISA Reagent for Detecting Crab Food Anaphylaxis - Xueni Qiu; Qiongyan Zhou; Xiaoxia Zhu; Wei Lin; Changkao Mu; Ronghua Li; Yangfang Ye; Weiwei Song; Ce Shi; Lei Liu; Huan Wang; Chunlin Wang; et al. (Journal of Ocean University of China, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Characterization of a newly identified RNA segment derived from the genome of Sclerotinia sclerotiorum reovirus 1 - Jichun Jia; Fan Mu; Yanping Fu; Jiasen Cheng; Yang Lin; Daohong Jiang; Jiatao Xie (Archives of Virology, 2022)

Design optimization of perforation on deflector for improved performance of vortex settling basin * - Zhuoyun Mu; Yiyi Ma; Lin Li (Irrigation and Drainage, 2022)
For vortex settling basins (VSBs) installed with a deflector, perforation is an effective retrofit to reduce the self‐weight of the deflector and sediment deposition on it. The current study investigated experimentally the performance of VSBs the deflector of which was perforated at different locations with various opening ratios. The results showed that perforating the outside overflow area of the deflector was the optimum for reducing sediment deposition. With an opening ratio of 8.67–13% in the outside overflow area of the deflector, the VSB exhibited similar sediment removal efficiency to the original design without any openings on the deflector. The current study provided the design optimization for deflector perforation in VSBs.

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Correction to: NLK is a key regulator of proliferation and migration in gallbladder carcinoma cells - Zhujun Tan; Maolan Li; Wenguang Wu; Lin Zhang; Qichen Ding; Xiangsong Wu; Jiasheng Mu; Yingbin Liu (Molecular and Cellular Biochemistry, 2021)

Making ERRFI1-Derived Peptides ‘Bindable’ to the Allosteric Dimerization Interface of Breast Cancer ERBB3 Kinase by Adding a Nonbonded Interaction System - Chenghong Ji; Jianmin Zhuang; Yizhou Jiang; Jiangang Mu; Longhai Lin; Yide Chen (International Journal of Peptide Research and Therapeutics, 2021)

Physical and Numerical Investigations on Wave Run-Up and Dissipation under Breakwater with Fence Revetment - Enjin Zhao; Lin Mu; Zhaoyang Hu; Xinqiang Wang; Junkai Sun; Zhiyong Zhang (Journal of Marine Science and Engineering, 2021)
Revetment elements and protective facilities on a breakwater can effectively weaken the impact of waves. In order to resist storm surges, there is a plan to build a breakwater on the northern shore of Meizhou Bay in Putian City, China. To better design it, considering different environmental conditions, physical and numerical experiments were carried out to accurately study the effects of the breakwater and its auxiliary structures on wave propagation. In the experiments, the influence of the wave type, initial water depth, and the structure of the fence plate are considered. The wave run-up and dissipation, the wave overtopping volume, and the structure stability are analyzed. The results indicate that the breakwater can effectively resist the wave impact, reduce the wave run-up and overtopping, and protect the rear buildings. In addition, under the same still water depth and significant wave height, the amount of overtopped water under regular waves is larger than that under irregular waves. With the increase of the still water depth and significant wave height, the overtopped water increases, which means that when the storm surge occurs, damage on the breakwater under the high tide level is greater than that under the low tide level. Besides, the fence plate can effectively dissipate energy and reduce the overtopping volume by generating eddy current in the cavity. Considering the stability and the energy dissipation capacity of the fence plate, it is suggested that a gap ratio of 50% is reasonable.

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

The ER membrane protein complex subunit Emc3 controls angiogenesis via the FZD4/WNT signaling axis - Mu Yang; Shujin Li; Wenjing Liu; Xiao Li; Yunqi He; Yeming Yang; Kuanxiang Sun; Lin Zhang; Wanli Tian; Lixin Duan; Huafu Chen; Dezhong Yao; et al. (Science China Life Sciences, 2021)

Temporal stability analysis of soil moisture along a coniferous forest hillslope with subtropical monsoon climate in southwest China - Yu-shi Bai; Mu-xing Liu; Jun Yi; Hai-lin Zhang (Journal of Mountain Science, 2021)

Grain size characteristics of the sand silt layers in the ancient delta of the dried Lop Nur lake (east Tarim Basin) and their environmental implications - Yongchong Lin; Guijin Mu; Lishuai Xu; Xue Zhao (Arabian Journal of Geosciences, 2021)

Frequent central Pacific La Niña events may accelerate Arctic warming since the 1980s - Jing Li; Lin Mu; Linhao Zhong (Acta Oceanologica Sinica, 2021)

Characterization of a novel botoulivirus isolated from the phytopathogenic fungus Sclerotinia sclerotiorum - Fan Mu; Jichun Jia; Yunxiang Xue; Daohong Jiang; Yanping Fu; Jiasen Cheng; Yang Lin; Jiatao Xie (Archives of Virology, 2021)

Maribacter hydrothermalis sp. nov., Isolated from Shallow-Sea Hydrothermal Systems Off Kueishantao Island - Huaying Lin; Dan Lin; Mu Zhang; Jianing Ye; Jia Sun; Kai Tang (Current Microbiology, 2021)

Flavonoids from Artemisia rupestris and their synergistic antibacterial effects on drug-resistant Staphylococcus aureus - Jiang-Er Lan; Xiao-Jin Li; Xiao-Feng Zhu; Zhong-Lin Sun; Jian-Ming He; Mire Zloh; Simon Gibbons; Qing Mu (Natural Product Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

A ~ 230-year dust storm record from China’s Lake Gonghai on the northeast Loess Plateau - Lishuai Xu; Dejun Wan; Yonghong Duan; Yongchong Lin; Guijin Mu; Zhilei Zhen; Yongsheng Yang (Arabian Journal of Geosciences, 2021)

Preliminary calibration results of the HY-2B altimeter’s SSH at China’s Wanshan calibration site - Chuntao Chen; Jianhua Zhu; Chaofei Ma; Mingsen Lin; Longhao Yan; Xiaoqi Huang; Wanlin Zhai; Bo Mu; Yongjun Jia (Acta Oceanologica Sinica, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

Distinct tropical Pacific sea surface temperature anomaly regimes enhanced under recent global warming - Jing Li; Lin Mu; Linhao Zhong (International Journal of Climatology, 2021)
El Niño and Southern Oscillation (ENSO) events are usually monitored by tropical Pacific sea surface temperature anomaly (SSTA) patterns with dramatic impacts on the global climate. To explore the diversity of the tropical Pacific SSTA, a novel method combined empirical orthogonal function analysis and the K‐means clustering algorithm is carried out to classify SSTA patterns during 1950–2016. Meanwhile, the total distance variance and total silhouette value are introduced to determine an optimal number of distinguishable representative SSTA patterns. Ten SSTA patterns are obtained, which shows frequent basin‐wide warming and extreme cold ENSO events in recent decades. It may be attributed to the changes in composition of the intrinsic modes along with the background mode of slowly increasing east–west SST gradient. The comparative analysis between periods 1950–1969 and 1997–2016 suggests that the two regimes of tropical Pacific SSTA, featured as extreme warm and moderate warm/extreme cold patterns respectively, become more distinct under recent global warming.

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

Overexpression of LncRNA PSMG3-AS1 Distinguishes Glioblastomas from Sarcoidosis - Liusheng Chen; Guanliang Wang; Zihui Xu; Kailong Lin; Sen Mu; Yicheng Pan; Mengya Shan (Journal of Molecular Neuroscience, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Mitigating arsenic accumulation in rice (Oryza sativa L.) using Fe-Mn-La-impregnated biochar composites in arsenic-contaminated paddy soil - Lina Lin; Minling Gao; Zhengguo Song; Haiyan Mu (Environmental Science and Pollution Research, 2020)

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

Performance of lab-scale microbial fuel cell coupled with unplanted constructed wetland for hexavalent chromium removal and electricity production - Chunxia Mu; Lin Wang; Li Wang (Environmental Science and Pollution Research, 2020)

Efficacy of fluopyram as a candidate trunk-injection agent against Bursaphelenchus xylophilus - Guangying Liu; Xu Lin; Shuangyu Xu; Guang Liu; Zhenyu Liu; Feng Liu; Wei Mu (European Journal of Plant Pathology, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Interaction between serine carboxypeptidase-like protein TtGS5 and Annexin D1 in developing seeds of Triticum timopheevi - Peihong Jiang; JianSheng Gao; Junyi Mu; Luning Duan; Yunsong Gu; Shichen Han; Lin Chen; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Cadmium immobilization in aqueous solution by Aspergillus niger and geological fluorapatite - Christopher Uche Okolie; Haoming Chen; Yexin Zhao; Da Tian; Lin Zhang; Mu Su; Zhonquan Jiang; Zhen Li; Huixin Li (Environmental Science and Pollution Research, 2020)

EFFECT OF A ROOT‐ZONE INJECTION IRRIGATION METHOD ON WATER PRODUCTIVITY AND APPLE PRODUCTION IN A SEMI‐ARID REGION IN NORTH‐WESTERN CHINA - Yan‐Ping Wang; Lin‐Sen Zhang; Yan Mu; Wei‐Hong Liu; Fu‐Xing Guo; Tian‐Ran Chang (Irrigation and Drainage, 2020)
Within the Chinese Loess Plateau, water resources are scarce and irrigation efficiency is a challenging issue. Traditional surface drip irrigation (SDI) methods have failed to improve irrigation efficiency and reduce surface evaporation in the region. An easy‐to‐install and practicable root‐zone injection irrigation (RII) method, with a low risk of emitter clogging and which uses subsurface infiltration‐promoting apparatuses (SIPA) to deliver water directly to the root zone, was designed and tested in an apple orchard over 3 years in northern Shaanxi, China. In the 0–0.6 m soil layer (where the apple roots are concentrated), the RII method produced consistently higher soil water content than the SDI method over all three growing seasons. The soil water content was consistently higher than 60% of field capacity, thus meeting the water requirements of fruit‐bearing apple trees. In addition, the RII method alleviated soil desiccation, significantly increased apple yields and improved fruit quality compared with the SDI method using the same volume of irrigation water. Both irrigation efficiency and water‐use efficiency were improved with the RII method. These results provide a theoretical basis for the utilization of the RII irrigation method in apple orchards in semi‐arid regions, which may improve water conservation and the sustainability of apple production. © 2019 John Wiley & Sons, Ltd.

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

High‐quality sea surface temperature measurements along coast of the Bohai and Yellow Seas in China and their long‐term trends during 1960–2012 - Yan Li; Lin Mu; Qingyuan Wang; Guoyu Ren; Qinglong You (International Journal of Climatology, 2020)
As semi‐enclosed and shallow seas, the Bohai and Yellow Seas (hereafter, BYS) marine ecosystems are more easily affected by natural and anthropogenic climate changes than those in the open oceans. An accurate assessment of sea surface temperature (SST) change is crucial for the near‐shore water environment. In this work, new high‐quality monthly mean SST time series from 11 in situ coastal hydrological stations at BYS for the period of 1960–2012 have been generated. Monthly mean SST time series were initially subjected to penalized maximal t (PMT) test, using homogeneous monthly mean surface air temperature (SAT) series as references. Homogenized monthly mean SST series were obtained by adjusting all significant change points which have been supported by historic metadata. Our study shows that there are 29 significant change points in these 11 SST series. The majority of them are caused by instrument changes and station relocations—both account for about 51.7 and 31%, respectively. Then, homogeneous SST series are used to assess the long‐term trends. As the regional average, the annual mean homogeneous SST series shows a rapid warming trend, with the rate of 0.21°C/decade. Compared to the homogeneous SST series, the original SST series underestimate the long‐term trend (only 0.13°C/decade), indicating the artificial change points usually result in a warm‐bias in the early period measurements. Seasonally, the most significant warming occurs in boreal winter during the period analysed. The relationships of the significant warming in boreal winter and atmospheric circulation modes have also been investigated. Results reflect the remarkable and direct influence of the East Asian Trough (EAT) on SST along the coastal BYS.

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Genome-wide identification of internal reference genes for normalization of gene expression values during endosperm development in wheat - Junyi Mu; Lin Chen; Yunsong Gu; Luning Duan; Shichen Han; Yaxuan Li; Yueming Yan; Xiaohui Li (Journal of Applied Genetics, 2019)

Implementation of the Land Surface Processes into a Vector Vorticity Equation Model (VVM) to Study its Impact on Afternoon Thunderstorms over Complex Topography in Taiwan - Chien-Ming Wu; Hsiao-Chun Lin; Fang-Yi Cheng; Mu-Hua Chien (Asia-Pacific Journal of Atmospheric Sciences, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

A structure–activity relationship study of phenyl sesquiterpenoids on efflux inhibition against Staphylococcus aureus - Zhong-Lin Sun; Tao Liu; Simon Gibbons; Qing Mu (Medicinal Chemistry Research, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

TLC-bioautography directed isolation of antibacterial compounds from active fractionation of Ferula ferulioides - Zhong-Lin Sun; Tao Liu; Shuang-Ying Wang; Xiao-Yue Ji; Qing Mu (Natural Product Research, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Novel mutations in ZP1, ZP2, and ZP3 cause female infertility due to abnormal zona pellucida formation - Zhou Zhou; Caixia Ni; Ling Wu; Biaobang Chen; Yao Xu; Zhihua Zhang; Jian Mu; Bin Li; Zheng Yan; Jing Fu; Wenjing Wang; Lin Zhao; et al. (Human Genetics, 2019)

Magnetic mineral diagenesis in sediments of saline lake Lop Nur - Wen Li; Gui-jin Mu; Yong-chong Lin; Hao-ze Song (Journal of Mountain Science, 2019)

Regulatory Roles of Peroxisomal Metabolic Pathways Involved in Musk Secretion in Muskrats - Meishan Zhang; Shuang Yang; Minghui Shi; Shumiao Zhang; Tianxiang Zhang; Yimeng Li; Shanghua Xu; Muha Cha; Yuping Meng; Shaobi Lin; Juan Yu; Xuxin Li; et al. (The Journal of Membrane Biology, 2019)

Permian integrative stratigraphy and timescale of China - Shuzhong Shen; Hua Zhang; Yichun Zhang; Dongxun Yuan; Bo Chen; Weihong He; Lin Mu; Wei Lin; Wenqian Wang; Jun Chen; Qiong Wu; Changqun Cao; et al. (Science China Earth Sciences, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

A new insight into lead (II) tolerance of environmental fungi based on a study of Aspergillus niger and Penicillium oxalicum - Da Tian; Zhongquan Jiang; Liu Jiang; Mu Su; Zheye Feng; Lin Zhang; Shimei Wang; Zhen Li; Shuijin Hu (Environmental Microbiology, 2019)
Summary Environmental microorganisms have been widely applied in heavy metal remediation. This study explored the mechanisms of lead tolerance of two typical filamentous fungi, Aspergillus niger and Penicillium oxalicum . It is shown that the mechanisms of reducing Pb toxicity by these two fungi have three major pathways. The secreted oxalic acid can react with Pb (II) to form insoluble Pb minerals, primarily lead oxalate. Then, the enhanced biosorption via forming new border of cell wall prevents the transportation of Pb (II) into hypha. In addition, the fungal activity could be maintained even at high Pb concentration due to the intracellular accumulation. It was confirmed that A. niger has the higher Pb tolerance (up to 1500 mg l −1 Pb level) compared with P. oxalicum (up to 1000 mg l −1 ). Meanwhile, Pb levels below 1000 mg l −1 partially stimulate the bioactivity of A. niger , which was confirmed by its elevated respiration (from 53 to 63 mg C l −1 medium h −1 ). This subsequently enhanced microbial functions of A. niger to resist Pb toxicity. A better understanding of Pb tolerance of these two fungi sheds a bright future of applying them to remediate lead‐contaminated environments.

The complete maternal mitochondrial genome sequence of Cuneopsis heudei (Bivalvia: Unionoida: Unionidae) - Qishuo Wang; Lu Ma; Lin Li; Ruijuan Feng; Huan Mu; Xin Wang; Cheng Wang; Xuepeng Wang (Conservation Genetics Resources, 2018)

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Identification and Field Evaluation of the Sex Pheromone of Orthaga achatina (Lepidoptera: Pyralidae) - Qi Yan; Hai-Dong Li; Yan Chen; Zhan-Feng Ye; Xi-Yu You; Jun Zhou; Lan-Fang Mu; Shi-Jing Liu; Xiang-Bo Kong; Sajjad Ali Khuhro; Shuang-Lin Dong (Journal of Chemical Ecology, 2018)

Drift analysis of MH370 debris in the southern Indian Ocean - Jia Gao; Lin Mu; Xianwen Bao; Jun Song; Yang Ding (Frontiers of Earth Science, 2018)

Scale effect and value criterion of the permeability of the interlayer staggered zones in the basalt of Jinsha River basin, China - Zhifang Zhou; Mu Lin; Qiaona Guo; Meng Chen (Hydrogeology Journal, 2018)

RNAi-mediated SLC7A11 knockdown inhibits melanogenesis-related genes expression in rabbit skin fibroblasts - Naisu Yang; Lin Mu; Bohao Zhao; Manman Wang; Shuaishuai Hu; Bin Zhao; Yang Chen; Xinsheng Wu (Journal of Genetics, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Assessment of the baseline sensitivity and resistance risk of Colletotrichum acutatum to fludioxonil - Yangyang Gao; Lifei He; Wei Mu; Beixing Li; Jin Lin; Feng Liu (European Journal of Plant Pathology, 2018)

Dose Verification for Tumor Motion with Different Treatment Planning Systems: A Dynamic Thorax Phantom Study - Shih-Neng Yang; Chun-Wei Lin; Mu-Bai Chang; Geoffrey G. Zhang; Kuei-Ting Chou; Yu-Rou Chiou; Shung-Shung Sun; Louis Lui; Tsung-Jung Ho; Tzung-Chi Huang (Journal of Medical and Biological Engineering, 2018)

Efficient Using Durian Shell Hydrolysate as Low-Cost Substrate for Bacterial Cellulose Production by Gluconacetobacter xylinus - Mu-Tan Luo; Cheng Zhao; Chao Huang; Xue-Fang Chen; Qian-Lin Huang; Gao-Xiang Qi; Lan-Lan Tian; Lian Xiong; Hai-Long Li; Xin-De Chen (Indian Journal of Microbiology, 2017)

Sensitivity of Colletotrichum acutatum to six fungicides and reduction in incidence and severity of chili anthracnose using pyraclostrobin - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Australasian Plant Pathology, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Long-term perceptions of outdoor thermal environments in an elementary school in a hot-humid climate - Wen-Mei Shih; Tzu-Ping Lin; Ning-Xin Tan; Mu-Hsien Liu (International Journal of Biometeorology, 2017)

The potential of fludioxonil for anthracnose control on China chili fruit - Yang-Yang Gao; Li-Fei He; Bei-Xing Li; Wei Mu; Jin Lin; Feng Liu (Phytoparasitica, 2017)

Artificial Inoculation Method of Pokkah Boeng Disease of Sugarcane and Screening of Resistant Germplasm Resources in Subtropical China - Ze-Ping Wang; Hai-Jun Sun; Qiang Guo; Shi-Qiang Xu; Ji-Hua Wang; Shan-Hai Lin; Mu-Qing Zhang (Sugar Tech, 2017)

CNOP-based sensitive areas identification for tropical cyclone adaptive observations with PCAGA method - Lin-Lin Zhang; Shi-Jin Yuan; Bin Mu; Fei-Fan Zhou (Asia-Pacific Journal of Atmospheric Sciences, 2017)

Definition of water exchange zone between the Bohai Sea and Yellow Sea and the effect of winter gale on it - Jun Song; Junru Guo; Jing Li; Lin Mu; Yulong Liu; Guosong Wang; Yan Li; Huan Li (Acta Oceanologica Sinica, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Propofol Prevents Hippocampal Neuronal Loss and Memory Impairment in Cerebral Ischemia Injury Through Promoting PTEN Degradation - Xin Chen; Ye-Mu Du; Feng Xu; Dai Liu; Yuan-Lin Wang (Journal of Molecular Neuroscience, 2016)

Recent research progress and prospects in tourism geography of China - Lin Lu; Jie Bao; Jianfeng Huang; Qijing Zhu; Chenglin Mu; Xiaole Chu; Yan Xu; Xiaoli Zha (Journal of Geographical Sciences, 2016)

Oasis microclimate effect on the dust deposition in Cele Oasis at southern Tarim Basin, China - Lishuai Xu; Guijin Mu; Xiao Ren; Dejun Wan; Junxia He; Yongchong Lin (Arabian Journal of Geosciences, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Panobinostat PK/PD profile in combination with bortezomib and dexamethasone in patients with relapsed and relapsed/refractory multiple myeloma - Song Mu; Yoshiaki Kuroda; Hirohiko Shibayama; Masayuki Hino; Takeshi Tajima; Claudia Corrado; Rong Lin; Edward Waldron; Florence Binlich; Kenshi Suzuki (European Journal of Clinical Pharmacology, 2016)

Alcohol consumption and rates of cancer screening: Is cancer risk overestimated? - Lin Mu; Kenneth J. Mukamal (Cancer Causes & Control, 2016)

Vertical motions of tide gauge stations near the Bohai Sea and Yellow Sea - ShouHua Liu; ChangLin Chen; KeXiu Liu; Lin Mu; Hui Wang; XinRong Wu; JianLi Zhang; XiaoFeng Duan; Jia Gao (Science China Earth Sciences, 2015)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Characterization of a Novel Two-Component System in Burkholderia cenocepacia - Callie R. Merry; Michael Perkins; Lin Mu; Bridget K. Peterson; Rebecca W. Knackstedt; Christine L. Weingart (Current Microbiology, 2015)

Expression screening and annotation of Sepiella maindroni ink sac cDNA library - WEI-WEI SONG; CHANG-KAO MU; SHAO CHU; YU-YU ZHANG; PING-PING ZHAN; CHUN-LIN WANG (Journal of Genetics, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Aerosolized bovine lactoferrin reduces lung injury and fibrosis in mice exposed to hyperoxia - Hsiao-Ling Chen; Chih-Ching Yen; Shih-Ming Wang; Tung-Chou Tsai; Zi-Lun Lai; Jheng-Yue Sun; Willei Lin; Wu-Huei Hsu; Chuan-Mu Chen (BioMetals, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Genetic variation at 8q24, family history of cancer, and upper gastrointestinal cancers in a Chinese population - Heather P. Tarleton; Shen-Chih Chang; Sungshim Lani Park; Lin Cai; Baoguo Ding; Na He; Shehnaz K. Hussain; Qingwu Jiang; Li-Na Mu; Jianyu Rao; Hua Wang; Nai-Chieh Y. You; et al. (Familial Cancer, 2014)

Aquatic predicted no-effect concentration for three polycyclic aromatic hydrocarbons and probabilistic ecological risk assessment in Liaodong Bay of the Bohai Sea, China - Ying Wang; Juying Wang; Jingli Mu; Zhen Wang; Ziwei Yao; Zhongsheng Lin (Environmental Science and Pollution Research, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Liver proteomic analysis of the large yellow croaker (Pseudosciaena crocea) following polyriboinosinic:polyribocytidylic acid induction - Yinnan Mu; Xiang Wan; Kebing Lin; Jingqun Ao; Xinhua Chen (Fish Physiology and Biochemistry, 2013)

Diagnosis of nervous necrosis virus in orange-spotted grouper, Epinephelus coioides, by a rapid and convenient RT-PCR method - Yinnan Mu; Kebing Lin; Xinhua Chen; Jingqun Ao (Acta Oceanologica Sinica, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Rural tourism development in China: Principles, models and the future - Ling-en Wang; Sheng-kui Cheng; Lin-sheng Zhong; Song-lin Mu; Bijaya G. C. Dhruba; Guo-zhu Ren (Journal of Mountain Science, 2013)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

NLK is a key regulator of proliferation and migration in gallbladder carcinoma cells - Zhujun Tan; Maolan Li; Wenguang Wu; Lin Zhang; Qichen Ding; Xiangsong Wu; Jiasheng Mu; Yingbin Liu (Molecular and Cellular Biochemistry, 2012)

Erratum to: NLK is a key regulator of proliferation and migration in gallbladder carcinoma cells - Zhujun Tan; Maolan Li; Wenguang Wu; Lin Zhang; Qichen Ding; Xiangsong Wu; Jiasheng Mu; Yingbin Liu (Molecular and Cellular Biochemistry, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Low-frequency variability of a semi-closed sea induced by the circulation in an adjacent ocean in a wind-driven, quasi-geostrophic, eddy-resolving simulation - Lin Mu; Linhao Zhong; Lijuan Hua; Jun Song (Ocean Dynamics, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Study on roughness coefficient for unsubmerged reed in the Changjiang Estuary - Fengfeng Gu; Lin Mu; Dingman Qi; Junhua Li; Lingshuang Kong; Yuanyang Wan (Acta Oceanologica Sinica, 2011)

Winter heat budget in the Huanghai Sea and the effect from Huanghai Warm Current (Yellow Sea Warm Current) - Lulu Qiao; Xiaohua Wang; Yongzhi Wang; Dexing Wu; Xianwen Bao; Lin Mu (Acta Oceanologica Sinica, 2011)

Numerical study of M2 internal tide generation and propagation in the Luzon Strait - Huan Li; Dan Song; Xueen Chen; Hongbao Qian; Lin Mu; Jun Song (Acta Oceanologica Sinica, 2011)

Vertical structure and seasonal variation of tidal and residual currents in the northern Huanghai Sea - Jun Song; Junru Guo; Lulu Qiao; Lin Mu; Zhigang Yao; Yang Liu; Huan Li; Xianwen Bao; Xiaoyan Sun; Jia Gao (Acta Oceanologica Sinica, 2011)

Lactoferrin: an iron-binding antimicrobial protein against Escherichia coli infection - Chih-Ching Yen; Chih-Jie Shen; Wu-Huei Hsu; Yi-Hsin Chang; Hsin-Tang Lin; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2011)

Arbuscular mycorrhiza regulate inter-specific competition between a poisonous plant, Ligularia virgaurea, and a co-existing grazing grass, Elymus nutans, in Tibetan Plateau Alpine meadow ecosystem - Liang Jin; Guiqi Zhang; Xiaojuan Wang; Cunyan Dou; Mu Chen; Shuangshuang Lin; Yuanyuan Li (Symbiosis, 2011)

A single amino acid substitution in PthA of Xanthomonas axonopodis pv. citri altering canker formation on grapefruit leaves - Hsin-Cheng Lin; Mu-Kuei Chu; Yuang-Chuen Lin; Wen-Ling Deng; Hsiang Chang; Shih-Tien Hsu; Kuo-Ching Tzeng (European Journal of Plant Pathology, 2011)

Effects of temperature and initial pH on biohydrogen production from food-processing wastewater using anaerobic mixed cultures - Yen-Hui Lin; Mu-Ling Juan; Hsin-Jung Hsien (Biodegradation, 2011)

Using Seven Types of GM (1, 1) Model to Forecast Hourly Particulate Matter Concentration in Banciao City of Taiwan - Tzu-Yi Pai; Ching-Lin Ho; Shyh-Wei Chen; Huang-Mu Lo; Pao-Jui Sung; Shu-Wen Lin; Wei-Jia Lai; Shih-Chi Tseng; Shu-Ping Ciou; Jui-Ling Kuo; Jing-Tang Kao (Water, Air, & Soil Pollution, 2011)

Ovate family protein 1 as a plant Ku70 interacting protein involving in DNA double-strand break repair - Yung-Kai Wang; Wen-Chi Chang; Pei-Feng Liu; Mu-Kai Hsiao; Chueh-Tsun Lin; Shih-Ming Lin; Rong-Long Pan (Plant Molecular Biology, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Physicochemical evolution and positive selection of the gymnosperm matK proteins - Da Cheng Hao; Jun Mu; Shi Lin Chen; Pei Gen Xiao (Journal of Genetics, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Molecular phylogeny, long-term evolution, and functional divergence of flavin-containing monooxygenases - Da Cheng Hao; Shi Lin Chen; Jun Mu; Pei Gen Xiao (Genetica, 2009)

Polymorphisms within promoter of Japanese flounder (Paralichthys olivaceus) ovary cytochrome P450-c19 (CYP19a) gene associated with reproductive traits - Feng He; Hai Shen Wen; Shuang Lin Dong; Bao Shi; Cai Fang Chen; Lian Shun Wang; Jun Yao; Xing Jiang Mu; Yu Guo Zhou (Fish Physiology and Biochemistry, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Impact of consistent boundary layer mixing approaches between NAM and CMAQ - Pius Lee; Youhua Tang; Daiwen Kang; Jeff McQueen; Marina Tsidulko; Ho-Chun Huang; Sarah Lu; Mary Hart; Hsin-Mu Lin; Shaocai Yu; Geoff DiMego; Ivanka Stajner; et al. (Environmental Fluid Mechanics, 2009)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Isolation and characterization of a novel thermophilic Bacillus strain degrading long-chain n-alkanes - Lei Wang; Yun Tang; Shuo Wang; Ru-Lin Liu; Mu-Zhi Liu; Yan Zhang; Feng-Lai Liang; Lu Feng (Extremophiles, 2006)

Interconversion Pharmacokinetics of Simvastatin and its Hydroxy Acid in Dogs: Effects of Gemfibrozil - Thomayant Prueksaritanont; Yue Qiu; Lillian Mu; Kimberly Michel; Janice Brunner; Karen M. Richards; Jiunn H. Lin (Pharmaceutical Research, 2005)

Temporal and spatial expression of biologically active human factor VIII in the milk of transgenic mice driven by mammary-specific bovine α-lactalbumin regulation sequences - Chuan-Mu Chen; Chih-Hong Wang; Shinn-Chih Wu; Chih-Cheng Lin; Shwu-Hwa Lin; Winston T.K. Cheng (Transgenic Research, 2002)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)